Melatonin inhibits ethylene biosynthesis by regulating MdERF1/MdERF3 pathway during apple fruit ripening - Chen Li; Qian Yu; Yanmin Du; Wenhui Wang; Yajing Si; Yuling Liang; Shijiao Lin; Guangxin Yang; Weiting Liu; Aide Wang; Yinglin Ji (Postharvest Biology and Technology, 2026)

Corrigendum to “Chemometrics- and AI-driven optical techniques for rapid detection of cereal grain toxins: an up-to-date comprehensive review (2020–present)” [Food Control 190 (2026) 112364] - Mengchao Lv; Qi Zhang; Hong-Ju He; Yuling Wang; Xingqi Ou (Food Control, 2026)

Chemometrics- and AI-driven optical techniques for rapid detection of cereal grain toxins: an up-to-date comprehensive review (2020–present) - Mengchao Lv; Qi Zhang; Hong-Ju He; Yuling Wang; Xingqi Ou (Food Control, 2026)

Elevated ferroptosis is associated with elevated T cells in patients with heat stroke - Qi Cui; Zhongyan Xu; Daxin Lei; Chao Yu; Yuling Luo; Jie Zheng; Fukun Wang (Molecular Biology Reports, 2026)

Methylome and transcriptome analysis reveal the impact of psychological stress on the skin - Bingjie Li; Ying Zou; Shenghua Tian; Laura Gonda; Andre Mahns; Tao Huang; Ludger Kolbe; Yuling Shi; Sijia Wang (Molecular Genetics and Genomics, 2026)

Colletotrichum aotearoa B. Weir & P.R. Johnst causing leaf anthracnose in Lithocarpus litseifolius in China - Yuling Wang; Chang Liu; Guolin Cai; Ning Shu; Ziqiang Luo; Zixuan Qiu; Wuping Yan (Crop Protection, 2026)

Spatially resolved multi-omics analysis of indigenous Bacillus-fortified high-temperature Daqu - Hao Shi; Yuling Shen; Qingqing Ye; Hui Yu; Maoling Tian; Hongmei Wang; Yang Wei; Shiying Yan; Yiping Chen; Jie Zhang; Shu Li; Yang Yang; et al. (Food Research International, 2026)

Three-dimensional thermal management: Biomass aerogel with super-hydrophilicity for high-efficiency solar evaporation via environmental energy synergy - Li Jiang; Yanyou Huang; Liangdong Ye; Yuling Lv; Ruibin Shen; Wei Wang; Yanlan Pan; Zuocai Zhang; Shaorong Lu (Desalination, 2026)

Enhanced nitrogen and phosphorus co-removal mediated by quorum sensing in novel cold-resistant strain LD-01: Mechanisms and application in hyporheic zones during freeze–thaw cycles - Dong Li; Yuling Zhang; Xiaosi Su; Tao Lang; Ruixin Wang; Yuliang Hu (Bioresource Technology, 2026)

Abrupt versus progressive CO2 increases: Overestimation of stimulatory effects on iron-driven anaerobic methane oxidation activity in paddy soils - Wangting Yang; Jinghao Jin; Evgenios Agathokleous; Qinan Hu; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Zhenghua Hu; Lidong Shen (Agriculture, Ecosystems & Environment, 2026)

Small-sample BOD₅ interval prediction for aeration recommendation using conformal calibrated LightTransformer-LGBM model - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Shuang Ren (Journal of Environmental Chemical Engineering, 2026)

Wheat properties shape microbial succession and flavor profile in high-temperature Daqu fermentation: a multi-omics perspective - Hongmei Wang; Yuling Shen; Sican Luo; Yongxin Hu; Fuli Wen; Qian Wang; Xi Shen; Hao Shi; Yiping Chen; Xiaozhong Zhong; Songtao Wang; Yang Wei; et al. (Food Research International, 2026)

Metabolic reprogramming for post-acidification control in fermented milk via post-sterilization treatment - Han Lu; Liru Cui; Menglu Li; Yuling Xue; Yannan He; Chang Liu; Yan Wu; Shijie Wang (Food Microbiology, 2026)

Divergent temporal dynamics of yield response to nitrogen fertilization across the three major cereals - Xiaowen Zhao; Meitong Wang; Baiheng Su; Yuling Li; Xiaohe Wang; Yu Jiang; Zhenghui Liu; Ganghua Li; Yanfeng Ding; Weiwei Li (Field Crops Research, 2026)

Incorporating dynamic ozone stress and parameter optimization into the BEPS model for improved GPP simulation - Jian Wang; Yuling Du; Jibo Yue; Tianxiang Cui; Yumin Chen; Lin Sun; Lei Shi (Ecological Modelling, 2026)

Heat stress memory in Porites lutea: Holobiont coordination and the molecular basis of thermotolerance - Yuling Ma; Xiaopeng Yu; Kefu Yu; Yue Zheng; Biao Chen; Zhenjun Qin; Zhiheng Liao; Lijia Xu; Yongzhi Wang (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Sustained-release salt reservoir enables durable solid electrolyte interphases for practical micron-sized silicon composite anodes - Kui Lin; Junke Wu; Zhengguang Song; Yuling Yi; Fuxi Peng; Shiwen Wang; Zhimin Zou; Tongbin Lan; Junxiong Wu; Chunhai Jiang (Chemical Engineering Journal, 2026)

An FcRn-mediated exosome-based oral vaccine enhanced co-mucosal immunity via targeting intestinal epithelial transport and lymphatic activation - Wei Zhang; Wen Guo; Caishun Chen; Meiqi Han; Yuling Mao; Siling Wang (Chemical Engineering Journal, 2026)

Consistent functional genes in methanogens along soil profiles in a temperate marshland - Yuling Tan; Nannan Wang; Kexin Li; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ming Yang; Wenwen Tan; Yuedong Guo; Yanyu Song; Fenghui Yuan; Xiaofeng Xu; et al. (Soil Ecology Letters, 2026)

Associations of pedogenic carbonate accumulation with soil organic-inorganic carbon coupling in arid croplands - Tongping Lu; Yuling Li; Xuhui Wang; Hui Guo; Bin He; Muhammad Shoaib Rana; Jie Ma; Changyan Tian; Jianfei Shi; Yugang Wang; Xiujun Wang (Agriculture, Ecosystems & Environment, 2026)

Freeze-thaw specifically regulates microbiome patterns and phosphorus acquisition strategies in the lake-groundwater interaction zone - Yuling Zhang; Ruixin Wang; Xiaosi Su; Tao Lang; Dong Li (Water Research, 2026)

Co-infection with CAV facilitates ALV-K replication and induces severe immunosuppression in chickens - Yuling Cui; Mengyue Dong; Zhanxin Wang; Yang Liu; Jiajia Liu; Hainuo Zeng; Runlin Shao; Ruiheng Liu; Yuanjia Liu; Qingmei Xie; Xinheng Zhang (Veterinary Microbiology, 2026)

Unveiling forest vertical structure across China through stratified effective plant area index using extensive UAV LiDAR and multi-source remote sensing data - Zhiyong Qi; Zitong Bai; Haitao Yang; Yao Wang; Kai Cheng; Zekun Yang; Ang Chen; Tianyu Xiang; Yu Ren; Yixuan Zhang; Yuling Chen; Qingpeng Wang; et al. (Remote Sensing of Environment, 2026)

Co-treatment of arsenic-rich dust and iron-bearing slag by reduction smelting: Arsenic immobilization, phase transformation, and environmental stability - Fei Chai; Jianhua Wang; Yuan Zhou; Zelin Fu; Yuling Tu; Yanjie Liang; Xiaobo Min; Liyuan Chai (Process Safety and Environmental Protection, 2026)

Genome-wide characterization of the apple WOX family identifies MdWOX13 as a repressor of fruit ripening - Yinglin Ji; Shijiao Lin; Mingqian Wang; Yuling Liang; Meili Xin; Yanan Wang; Weiting Liu; Aide Wang; Bin Li (Postharvest Biology and Technology, 2026)

Preliminary insight into the ability of bovine-derived Loigolactobacillus coryniformis XJ-C-L1-produced acid-dependent extracellular metabolites to inhibit MRSA growth and biofilm formation in milk - Yuling Guo; Wenjing Wang; Yaqian Liang; Meihui Tian; Ming Wu; Junkai Wang; Haihong Hao; Yu Pan (International Dairy Journal, 2026)

Legume dominance and context-dependent benefits of cover crops for nitrogen supply in global agriculture - Xiaowen Zhao; Yuling Li; Meitong Wang; Baiheng Su; Chongxi Wen; Xiaohe Wang; Ganghua Li; Ziting Wang; Yanfeng Ding; Weiwei Li (European Journal of Agronomy, 2026)

Using transgenic zebrafish to assess the effects of SCCPs exposure on embryonic neural development and its potential mechanisms - Jinxian Yang; Ruiyao Huang; Jin Wang; Mengna Jiang; Fengxu Wang; Yuling Jiang; Jiaxin Liu; Mingjing Sun; Sheng Chen; Tian Zhou; Xinyuan Zhao; Shunxing Zhu (Chemico-Biological Interactions, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Seawater eDNA and Underwater Visual Surveys Reveal Genus-Level Reef-Building Coral Communities in the Wanshan Archipelago, South China Sea - Jiabin Guo; Lan Yang; Zhihui Qin; Anxin Lu; Yuling Ma; Yue Zheng; Biao Chen; Zhenjun Qin; Zhiheng Liao; Lijia Xu; Yongzhi Wang; Kefu Yu; et al. (Fishes, 2026)
Environmental DNA (eDNA) metabarcoding is increasingly used as a complementary tool for coral biodiversity assessment, but its performance in subtropical, estuary-influenced reef systems remains insufficiently tested. This study combined seawater eDNA metabarcoding with concurrent underwater visual surveys and historical records to assess reef-building scleractinian corals in the Wanshan Archipelago, Pearl River Estuary. In June 2022, surface and bottom seawater samples were collected from seven sites, yielding 14 eDNA samples, and dive-based photographic surveys were conducted concurrently. A universal 18S rRNA assay was used for high-throughput sequencing, and eDNA detections were compared with visual and historical survey data at the genus level. eDNA detected 13 families and 21 genera, with Porites and Echinopora as dominant genera. eDNA recovered more genera than concurrent visual surveys in all five regional comparisons, although the two methods yielded overlapping but partly distinct genus inventories. Surface-water eDNA showed a slight, site-dependent advantage in genus recovery and overlap with concurrent visual surveys, whereas correspondence with historical records varied among regions; surface and bottom samples shared most genera but also contributed complementary layer-specific detections. Community composition showed spatial clustering broadly consistent with geographic proximity. These findings indicate that seawater eDNA provides complementary genus-level information and support paired surface- and bottom-water sampling for a more complete exploratory characterization of coral diversity in complex subtropical coastal reef systems.

Synthetic microbial community shields wheat from cadmium: Coordinating host metabolic reprogramming and rhizosphere microenvironment regulation - Huangxin Chen; Lin Kong; Yaoyuan Zhang; Guiyin Wang; Xin Qi; Changlian Xu; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Journal of Hazardous Materials, 2026)

Adaptive mechanisms of scleractinian corals against low-salinity stress: Insights from molecular regulation and natural acclimation in the Pearl River Estuary - Lijia Xu; Junling Chen; Yongzhi Wang; Yuling Ma; Yue Zhen; Biao Chen; Zhenjun Qin; Zhiheng Liao; Xiaopeng Yu; Kefu Yu (Journal of Environmental Sciences, 2026)

Effect of heat-moisture modified sweet potato starch on the microstructure and physicochemical properties of wheat noodles - Wei Wang; Dongdong Huang; Yuling Ma; Yiying Yang; Aijun Hu; Haiyan Gao (Journal of Cereal Science, 2026)

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

Explainable machine learning-based study on the applicability of thermal indicators for university classrooms in summer - Luyao Wang; Fan Fei; Yan Wang; Yongwei Song; Yuling Xiao; Weidong Wu; Kunkun Zhao; Hiroatsu Fukuda (Building and Environment, 2026)

Antibacterial mechanisms of terpinen-4-ol against Aeromonas hydrophila - Kaiqi Lian; Xiangfeng Meng; Yuhang Wang; Shengming Ma; Xiaolong Li; Ren Ren; Yuling Liu; Lingling Zhou; Renhai Peng (Archives of Microbiology, 2026)

Coastal marsh conversion to paddy fields leads to a more pronounced stimulation of temperature sensitivity of soil microbial respiration in higher-latitude regions - Xiaochen Yao; Weiqi Wang; Yuling Yang; Wangting Yang; Bingjie Ren; Qinan Hu; Lidong Shen (Marine Pollution Bulletin, 2026)

Natural polyphenol-mediated oxidative polymerization and degradation of emerging contaminants - Yangju Li; Hexian Qin; Jiansen Lei; Meimei Wang; Yuling Ren; Dapeng Wu; Haoran Dong (Critical Reviews in Environmental Science and Technology, 2026)

Camel milk-derived Lentilactobacillus parabuchneri L-185 produces acid-associated metabolites that inhibit MRSA growth and biofilm formation in milk - Wenjing Wang; Yuling Guo; Junkai Wang; Yaqian Liang; Meihui Tian; Yitao Li; Hui Zhang; Haihong Hao (International Journal of Food Microbiology, 2026)

Enhanced puncture event detection for teleoperated needle insertion robotic system - Hongbing Li; Yubin Lan; Yuling Li; Linlong Li; Rui Wang (Medical & Biological Engineering & Computing, 2026)

Improving embryo rescue efficiency in seedless grape breeding with zeatin - Xi Chen; Shaopeng Zhao; Xinyu Chen; Mengyu Ma; Xue Wen; Yao Xiao; Yong Wang; Yuling Li; Feng Sun; Guotian Liu; Tingting Chen; Yan Xu (Protoplasma, 2026)

Characteristics of soil organic carbon and its stability under different vegetation types and restoration years in Hongze lake wetland, China - Yanan Bai; Haikun Wu; Huifeng Lu; Yuling Yang; Yanping Wang; Lei Dai; Yuchun Ma; Jinqi Wang; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Elevated CO2 synergizes with nanoplastics to intensify arsenic mobilization, biotransformation, and plant uptake in soil-spinach systems - Wei Li; Yabo Wang; Yuling Suo; Zishu Zheng; Qiao Xu; Meiling Xu; Fen Xu; Weiqin Yin; Shengsen Wang; Xiaozhi Wang (Environmental Pollution, 2026)

Prepare the umbrella before it rains: Transmission and rescue strategy of extreme climate shocks via susceptible-infectious-recovered-susceptible model - Qian Wang; Fang Nan; Yuling Luo (Ecological Economics, 2026)

Ameliorative Effects of an Antioxidant and Anti-Inflammatory Limosilactobacillus fermentum TG017 on DSS-Induced Ulcerative Colitis in Mice - Qianhao Hou; Yuling Li; Zuanyuan Huang; Honghua Hu; Xin Li; Jinyuan Zhang; Wenying Duan; Songsong Pan; Zetian Wang; Xiaodong Liu; Wei Xu; Lijun Liao (Probiotics and Antimicrobial Proteins, 2026)

Transcription factor McORA activates McHDR to enhance aphid-repelling (E)-β-farnesene biosynthesis in Matricaria chamomilla L. - Honggang Wang; Jin Wang; Wenjing Cheng; Siqing Zhu; Qianlan Liu; Yuling Tai; Yi Yuan (Plant Cell Reports, 2026)

Characteristics and Mechanisms of Crack Propagation in Gas-Bearing Coal Under Adsorptive Versus Non-Adsorptive Gas Conditions - Dengke Wang; Yixuan Tang; Wenrui Li; Hongtu Zhang; Biao He; Furu Kang; Shixing Fan; Baisheng Nie; Yuling Xia; Xiaofei Pang; Jinhao Yu (Natural Resources Research, 2026)

Development and Validation of An HPLC Method for Isolation and Structural Elucidation of Impurities in Chlorogenic Acid Self-Microemulsion Formulations - Yue Gao; Yanan Wang; Jing Xu; Ming Ji; Dongyang Zhao; Yanqi Han; Longhui Hao; Yi Zhang; Ying Sun; Zhenshuai Qin; Jun Ye; Hongliang Wang; et al. (Journal of Pharmaceutical Innovation, 2026)

Clinical study on the interaction between iron metabolism and neuroinflammation and iron deposition in the substantia nigra of Parkinson’s disease - Yani Yao; Jiayi Li; Jiaoyang Yan; Qian Cai; Yuling Wang; Huan Xia; Tingting Feng; Peishan Li; Xinling Yang (Brain Imaging and Behavior, 2026)

Hydrocarbon subsidy-stress and divergent reduced iron–manganese thresholds shape microbial resilience in anoxic aquifers - Jili Wang; Yuling Zhang; Yang Ding; Dong Li; Yi Zhang (Water Research, 2026)

The pulse of ancient fires: Reconstructing Toarcian wildfire regimes from fossil charcoals in northwest China - Yuling Na; Xiao Shi; Chi Tian; Wenpei Pei; Qianqian Song; Shaoting Tian; Bing Wang; Yan Liu; Leon Nahuel Torres; Jianxin Yu (Review of Palaeobotany and Palynology, 2026)

Evidence for Early Middle Jurassic wildfires: New macro-charcoal records from the Xishanyao Formation, Junggar Basin, Northern Xinjiang, China - Bing Yang; Yuling Na; Xiao Shi; Yi Wei; Xinzhi Zhang; Bing Wang; Siyuan Sun; Weitong Li (Review of Palaeobotany and Palynology, 2026)

Understanding the tradeoff between the flood risk and the hydropower benefit from the integrated flood control operation of a reservoir group and a flood detention basin - Zhenyu Mu; Dedi Liu; Zhenyu Wang; Yuling Zhang; Pan Liu; Lihua Xiong; Jie Chen; Hua Chen; Jiabo Yin (Journal of Hydrology, 2026)

l-Lysine effects on myosin carbonylation in metal-catalyzed oxidation: Implications for thermal gelation - Yuling Liu; Yuqi Wu; Ge Han; Jiaxin He; Yawen Wang; Jinfeng Pan; Shengjie Li (Food Research International, 2026)

Metagenomic and metabolomic insights into microbial-metabolite interactions underlying flavor formation in Hebei-style soybean paste fermentation - Chang Liu; Jingjing Hao; Han Lu; Pingping Ma; Yannan He; Yuling Xue; Zhiyuan Kang; Shijie Wang (Food Research International, 2026)

Efficient biosynthesis of vitamin B6 based on DXP-independent pathway in Bacillus subtilis - Lingqing Zeng; Jiawei Sun; Yuling Chen; Yongzhong Wang; Yingwu Yang (Food Bioscience, 2026)

Stretchable multifunctional composite films with ultra-high conductivity for sustainable heating, EMI shielding, and antimicrobial applications - Yuling Lv; Yanyou Huang; Liangdong Ye; Ruibing Shen; Li Jiang; Wei Wang; Shaorong Lu (Chemical Engineering Journal, 2026)

Microbial synergy for uranium (VI) reduction in woodchip-sulfur mixotrophic biosystems - Yangmei Fei; Mengqi Wang; Yuling Zhu; Jiamin Huang; Zuozhen Han; Baogang Zhang (Chemical Engineering Journal, 2026)

Shoot apical meristem-dependent adventitious bud induction from embryo axes of castor bean (Ricinus communis L.) via optimized cytokinin-auxin ratio - Liang Bai; Liying Shan; Jian Song; Mengchen Xu; Yue Wang; Ruiyan Guo; Yanli Jin; Yangguang Duan; Yuling Zhang; Zhimin Jiang; Jilong Zhong; Yan Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Mercury dynamics and speciation in paddy soils irrigated with acid mine drainage from abandoned coal mine: Insights from vertical profiling - Shasha Liu; Longchao Liang; Xiaohang Xu; Yuling Kuang; Le Wang; Guangle Qiu; Zhuo Chen; Xian Dong; Jialiang Han (Acta Geochimica, 2026)

Advances on Sporisorium reilianum: microbiology along with chemistry, bioactivity, and application - Yihua Wang; Yansong Meng; Zezhuang Hao; Haohan Yang; Zhixin Shen; Denghui Yu; Ye Wang; Shuguang Guan; Yuling Ding; Yong Li (Folia Microbiologica, 2026)

Proteomic characterization of feather decorations and extinct buffalo glue during early Iron Age China - Binjie Qi; Zhiguo Zhang; Jiajun Wang; Zhipeng Li; Yuling He; Shishan Niu; Xiaomeng Li; Huiyun Rao; Yimin Yang (Science Bulletin, 2026)

Assessing spatiotemporal dynamics and future evolution of surface water quality in Zhejiang Province, China - Feng Jiang; Xiaoyi Shi; Yuling Xu; Zhenyi Jia; Jie Wang; Zhenzhen Zhang; Hongmei Yu; Yanlong Kong (Journal of Hydrology, 2026)

Breaking acidification-ammonia inhibition cycle in anaerobic co-digestion with alkaline lime mud via synthetic microbial consortium - Linpei Liu; Yao Ren; Xiaoru Chen; Jun Wang; Yuling Huang; Pan Zhang; Qili Zhu; Han Qin; Furong Tan; Mingxiong He; Yong Zhuang (Journal of Environmental Chemical Engineering, 2026)

Cellulose-based ultralight foam with dual-scale porosity from hybrid fibers for sustainable oil-water separation - Weiqiang Li; Jingge Liu; Meiying Li; Haitao Lin; Jian Fang; Xiaoqiao Wang; Jianchu Xu; Yuling Li; Junze Zhang; Xinheng Li; Gang Li (Carbohydrate Polymers, 2026)

Development of a high ethyl hexanoate-producing strain via ARTP mutagenesis and fermentation optimization using agricultural by-products - Yuling Li; Zhiqiang Wang; Renzhi Wan; Xin Zeng; Bingyue Xin; Biao Zhang; Jie Qiao; Deyin Zhao; Mingtao Zhao; Youyu Xie; Zhuangzhuang Jiang; Huawei Zeng; et al. (Biocatalysis and Agricultural Biotechnology, 2026)

Tryptophan metabolism alterations in neurological and psychiatric diseases: Molecular mechanisms and pharmacological targets - Yuanyuan Wang; Yuling Chen; Hongtao Li; Jingjing Sang; Chen Chen; Lei Xu; Weiting Zhang; Baichen Xiong; Ruijia Jiang; Xinyu Ren; Yao Chen; Haopeng Sun; et al. (Metabolic Brain Disease, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

A decision support system for coagulant dosage using explainable NSGA-II optimized stacking framework - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Ren Shuang (Journal of Water Process Engineering, 2026)

Characteristics of sediment microbial community structure under different vegetation types with various restoration durations in Hongze Lake - Yuhan Jin; Wangting Yang; Yuling Yang; Yanping Wang; Huaiping Ling; Sile Wen; Bingjie Ren; Xiuling Zhang; Zhenfa Su; Jinghao Jin; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Assessing the variations of the available flood storage capacity in a flood retention basin due to the changing environment - Yuling Zhang; Dedi Liu; Zhenyu Wang; Zhenyu Mu; Jiaoyang Wang; Pan Liu; Lihua Xiong; Jie Chen; Hua Chen (Journal of Environmental Management, 2026)

Adjusting fertilization depth for sustainable potato production in arid and semi-arid regions - Zhaoyang Li; Yukang Wang; Nan Shi; Yixuan Yuan; Lianjun Wei; Weixing Shan; Medelbek Meruyert; Ansabayeva Assiya; Zhikuan Jia; Kadambot H.M. Siddique; Ruixia Ding; Peng Wu; et al. (Field Crops Research, 2026)

Multistimuli-responsive degradable metal-organic framework nanoplatform potentiates photoimmunotherapy for hepatocellular carcinoma via cGAS-STING pathway activation - Yahui Wu; Zhipu Liu; Yi Zhang; Senfeng Zhao; Miaoqing Li; Ruiyang Zhang; Jiahui Cao; Peng Liu; Liming Song; Yin Liu; Yunpeng Zhai; Weijie Wang; et al. (Chemical Engineering Journal, 2026)

Epicoccum sorghinum as a leaf spot disease-causing pathogen in Lithocarpus litseifolius in China - Yuling Wang; Meng Li; Changjiang Liu; Guolin Cai; Mengxing Wang; Wuping Yan; Jianfeng Chen (Crop Protection, 2026)

Effects of stocking density on growth and glucose metabolism in rainbow trout (Oncorhynchus mykiss) - Zhao Li; Zhuohang Feng; Shuangyue Luo; Yaxin Wang; Yuling Xu; Kang Dong; Zhishuai Hou; Qinfeng Gao; Shuanglin Dong (Aquaculture, 2026)

Adsorptive Removal of Ibuprofen from Aqueous Solution by UiO-66: Performance Evaluation and Mechanistic Insights - Luo Xinzeng; Liu Yuling; Wang Zhuoran; Rong Wang; Hao Shu; Hongli Wang (Water, Air, & Soil Pollution, 2026)

Dynamic Changes in Serum Biochemical Indices and Alternative Splicing Events Revealed Molecular Regulatory Mechanisms in Rainbow Trout Under Copper Stress - Junhao Lu; Jinqiang Quan; Jing Zhou; Yucai Pan; Jiahui Zhang; Ziguo Wang; Yuling Qu (Marine Biotechnology, 2026)

Comammox Nitrospira dominates autotrophic nitrification in paddy fields under long-term fertilization - Bingjie Ren; Yanping Wang; Yuchao Wang; Yuling Yang; Zhenfa Su; Haikun Wu; Wangting Yang; Yuhan Jin; Jinghao Jin; Shuai Liu; Lidong Shen; Xu Zhao (Agriculture, Ecosystems & Environment, 2026)

Differential clinical factors influencing the effectiveness of distinct biologic agents in psoriasis: insights from a prospective cohort study in China - Min Dai; Yuxiong Jiang; Yuanyuan Wang; Dawei Huang; Yu Wang; Yifan Hu; Yunlu Gao; Qian Yu; Yuling Shi (Inflammation Research, 2026)

Seaweed and shellfish mariculture as nature-based solutions: Mitigating nutrient pollution from coastal fish mariculture and sewage - Yuling Yang; Yonglong Xiong; Tengteng Wang; Junxiao Zhang; Lan Feng; Guang Gao (Marine Pollution Bulletin, 2026)

Interpretable machine learning model based on floc images for monitoring the coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Peng Guo; Chuanchuan Dou; Wangben Zhao (Process Safety and Environmental Protection, 2026)

Divergent genomic characteristics and convergent metabolic phenotypes associated with Cd tolerance and soil Cd immobilization in multifunctional bacteria - Nei Wu; Yuling Yang; Jianming Xu; Haizhen Wang (Journal of Hazardous Materials, 2026)

Physicochemical properties, microbial diversity, metabolites and their potential relationships of traditional Chinese Zhacai fermented for different periods - Xinyi Wang; Yuanli Luo; Yuanqing Gu; Ting Ren; Yuling Liu; Xinhui Wang; Nan Zhao; Xin Nie; Dayu Liu; Zhiping Zhao (International Journal of Food Microbiology, 2026)

Hybrid evaporative-fan cooling vest: multi-scale cooling performance evaluation - XingLan Wang; Guang Yang; ShouXin Zhang; XiaoShan Yan; Yuling Luo; Suqin Chang; Xiaohui Zheng (Energy and Buildings, 2026)

An epoxy-based composite coating with CoFeNi/N-doped carbon for integrated flame retardancy, photothermal conversion, and microwave absorption in thermal management - Biyu Huang; Yuling Wang; Yusheng Tong; Jie Shen; Haopeng Zhang; Lei Liu; Meng Liu; Shaoxiang Li; Chuanmei Jiao; Xilei Chen (Chemical Engineering Journal, 2026)

Causal links between pandemics and weather and air pollution in 39 cities, 2020–2021 - Ting Shi; Bo Zhou; Ailin Qi; Kai Wang; Yunpeng Ao; Chenyi Li; Yuling Zhang (Atmospheric Pollution Research, 2026)

Mechanistic insights into isopropyl myristate-stimulated monascus pigment biosynthesis via untargeted metabolomics - Renzhi Wan; Zhiqiang Wang; Yuling Li; Xin Zeng; Bingyue Xin; Jie Qiao; Huawei Zeng; Liang Zhang (World Journal of Microbiology and Biotechnology, 2026)

Effect of organic amendments on soil organic carbon fractions, water retention, and mechanical properties in a Chinese Alfisol - Yue Pan; Danyang Wang; Tingting Tan; Jing An; Xinxin Jin; Hongtao Zou; Yuling Zhang; Na Yu; Kadambot H.M. Siddique (Soil and Tillage Research, 2025)

Stimulation of nitrate-driven AOM potential in paddy soils under elevated atmospheric CO2 concentration - Jinghao Jin; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Wangting Yang; Qinan Hu; Lidong Shen; Zhenghua Hu (Journal of Environmental Management, 2025)

Antimicrobial mechanism of moderate-temperature-assisted high-voltage pulsed electric field combined with vanillin against Saccharomyces cerevisiae and its application in red raspberry juice - Yuling He; Bin Li; Xiyun Sun; Xu Xie; Junwei Huo; Fuzhi Xuan; BaoRu Yang; Ying Zhou; Yuehua Wang (Innovative Food Science & Emerging Technologies, 2025)

Machine learning-assisted identification of core flavor compounds and prediction of core microorganisms in fermentation grains and pit mud during the fermentation process of strong-flavor Baijiu - Jiang Xie; Jiaxin Hong; Chunsheng Zhang; Xin Yuan; Zhigang Zhao; Dongrui Zhao; Shimin Wang; Baoguo Sun; Ran Ao; Jinyuan Sun; Yuling Sun; Mingquan Huang; et al. (Food Chemistry, 2025)

Combining deep learning and protein engineering to develop a thermostable protease for aquafeed applications - Zipeng Wu; Yuling Wang; Yiran Lao; Yutong Gao; Lingjie Kong; Han Jiang; Yuyang Zou; Peizhi Gu; Mingtao Huang; Xiufang Liu; Tao Wei (Food Bioscience, 2025)

All-in-one electrochromic windows based on hydrogels containing dual redox pairs for affordable and large-scale applications - Yuling Zhu; Qi Zhao; Chenglong Mu; Yahui Liu; Yuguo Xia; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Ether-free PDMS-based composite electrolytes with intrinsic safety, high ionic conductivity and wide electrochemical window for solid state Li-metal batteries - Chenglong Mu; Jinyan Chen; Qi Zhao; Yahui Liu; Yuling Zhu; Zhang Dai; Xina Sui; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Trophic status impacts the potential significance of anaerobic methane oxidation driven by multiple electron acceptors in Lake Taihu sediments - Wangting Yang; Qinan Hu; Hechen Huang; Jinghao Jin; Bingjie Ren; Sile Wen; Yuling Yang; Yefan He; Yanping Wang; Yanan Bai; Yuzhi Song; Lidong Shen (CATENA, 2025)

Anthropogenic aerosol feedbacks intensify air pollution and weather variability over China - Jixiang Li; Haipeng Yu; Andrea Pozzer; Kai Tang; Chenhui Jia; Zeyong Hu; Siyu Chen; Yunsai Zhu; Yuling Hu; Bofei Zhang; Hongyu Luo; Zekui Jiang; et al. (Atmospheric Environment, 2025)

Microalgae-induced changes in the rhizosphere microbiome improve saline-alkali tolerance of Perilla frutescens - Yunmei Zhang; Shuiwen Luo; Xuyang Gu; Wenshan Gao; Chenxing He; Ziyi Wang; Menghang Cheng; Yuling Liang; Dandan Cao; Jianfeng Liu (Journal of Applied Phycology, 2025)

EGF/ERBB2 blocks the endoplasmic reticulum-associated degradation to facilitate chronic obstructive pulmonary disease development by decreasing FAM8A1 via up-regulating DNMT3A - Ruonan Lv; Jing Wang; Mingrui Wan; Yuling Wang; Yanan Zhang (Functional & Integrative Genomics, 2025)

Genome-wide identification and functional analysis of the polyamine metabolism-related genes in Foxtail millet (Setaria Italica L.) - Liuan Hao; Tao Wang; Yangyang Wei; Pengtao Li; Yuling Liu; Quanwei Lu; Huawen Zou; Renhai Peng (Functional & Integrative Genomics, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Genome-wide identification and functional analysis of TCX gene family and the critical role of GhTCX17 in response to drought and salt stress in cotton - Yangyang Wei; Jingjing Zhai; Shuaikang Geng; Shaoliang Zhang; Yongqing Zhao; Bingkai Cui; Huiyun Shan; Yanhua Li; Cong Wang; Pengtao Li; Yuling Liu; Quanwei Lu; et al. (Functional & Integrative Genomics, 2025)

High-throughput discrimination of chlorogenic acid isomers in Lonicerae Japonicae Flos by U-shaped mobility analyzer-mass spectrometer - Meng Ding; Luwei Zheng; Ao Zhou; Yuling Li; Yiming Wang; Xiaoqiang Zhang; Wenjian Sun; Wen Gao; Ping Li; Hua Yang (Food Chemistry, 2025)

Confinement-effect adsorbents based on titanium-based lithium ion sieve for efficient lithium adsorption under natural pH conditions - Yuling Ma; Yu Han; Yan Yang; Tao Zhang; Jinxin Yao; Yuchen Li; Yongchen Zong; Wei Wang (Chemical Engineering Journal, 2025)

Cascade nanozyme of multi-antioxidant Mn-doped carbon dots counters cytokine storm in acute lung injury - Pengli Gao; Hongchengcheng Chen; Yuling Bai; Jiaqian Li; Xiaoli Wang; Jingying Jiang (Chemical Engineering Journal, 2025)

Molecular design of polyoxovanadate cathodes for advanced AZIBs: Multielectron redox chemistry and structural engineering - Yu Zhang; Tiantian Guan; Fan Yang; Qing Han; Lingling Xie; Xuejing Qiu; Lei Wang; Hongjun Chen; Yuling Wang; Xiaobo Ji; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Human Cortical Organoids with a Novel SCN2A Variant Exhibit Hyperexcitability and Differential Responses to Anti-Seizure Compounds - Yuling Yang; Yang Cai; Shuyang Wang; Xiaoling Wu; Zhicheng Shao; Xin Wang; Jing Ding (Neuroscience Bulletin, 2025)

The impact of COVID-19 pandemic on the etiological spectrum of respiratory infections in children - Jing Wang; Yuling Han; Xiaoling Wei; Yanqin Liu; Hua Zhang; Xiang Ma (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Demethylase MpAlkB2 negatively regulates the growth and positively regulates the synthesis of mycotoxin citrinin in Monascus purpureus - Yuling Chen; Tiaoshuang Qiu; Yongzhong Wang; Yingwu Yang (Archives of Microbiology, 2025)

Cuproptosis is involved in small intestinal toxicity in the paraffins during pregnancy - Juan Tang; Zemin Xu; Mengna Jiang; Chao Luo; Xiaoyan Li; Yuling Jiang; Yi Qu; Jialing Ruan; Xiaoke Wang; Meihua Zheng; Wing-Cheung Law; Xinyuan Zhao (Toxicology Letters, 2025)

A general chopping peak function for a reservoirs group flood control regulating - Zhenyu Mu; Dedi Liu; Zhenyu Wang; Yuling Zhang; Lihua Xiong; Jie Chen; Hua Chen; Jiabo Yin (Journal of Hydrology, 2025)

Novel insights into the morphological effects of trace organic contaminants on water/PhAC selectivity in nanofiltration of sewage - Junhao Zhao; Yanan Wang; Zuqiong Jiang; Yuefei Song; Nan Deng; Yuling Ren; Ronghua Ma; Kai Jiang (Journal of Hazardous Materials, 2025)

A novel nonaerated passive constructed wetland for high-efficiency nitrogen and phosphorus removal based on slow-release oxygen regulation - Bing Liao; Xinyu Quan; Yuling Yang; Xinrui Huang; Ziyi Wang; Zhicheng Pan (Journal of Environmental Chemical Engineering, 2025)

The rhizosphere as a hotspot for nitrite- and nitrate-dependent anaerobic oxidation of methane in paddy fields - Yanping Wang; Yanan Bai; Lidong Shen; Bo Shang; Yang Ji; Xupeng Miao; Bingjie Ren; Yuling Yang; Wangting Yang; Zhaozhong Feng (Environmental Pollution, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Cobalt-doped zinc phosphides regulated by phytic acid effects on the electrochemical activity of sensing clothianidin - Peiyuan Wei; Wei Han; Lingling Xie; Hongjun Chen; Yuling Wang; Limin Zhu; Baoshan He; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Huang Lian Jie Du Decoction Prevents Chronic Alcoholic Encephalopathy and Improves Gut Microbiota Imbalance in Mice - Yun Chen; Lianyan Jiang; Yuan Zhang; Yuling Shen; Mao Li; Dongdong Yang; Bo Wang (Molecular Neurobiology, 2025)

Tissue-specific effects of stocking density on fatty acid composition and liver metabolism in rainbow trout (Oncorhynchus mykiss) - Zhao Li; Kang Dong; Yuling Xu; Yaxin Wang; Zhishuai Hou; Qinfeng Gao; Shuanglin Dong (Fish Physiology and Biochemistry, 2025)

Regulation of coagulant dosage in water treatment based on explainable integrated time-series deep learning models - Wangben Zhao; Yuling Liu; Ren Shuang; Wang Lu; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Process Safety and Environmental Protection, 2025)

Investigation of the dynamics and influencing factors of deepwater condensate field leakage - Qiuyan Wang; Xuerui Zang; Xiaoming Luo; Ce Wang; Yuling Lü (Process Safety and Environmental Protection, 2025)

Degradation of thiamphenicol by electroactive biofilm coupled with N-MnO2 modified layer double hydroxides as cathode in microbial fuel cell - Junfeng Chen; Yuling Xu; Xinyi Zhang; Feng Lan; Yuchen Cao; Yanyan Liu; Renjun Wang; Yuewei Yang (Journal of Environmental Management, 2025)

Human FABP7 selectively captures docosahexaenoic acid over eicosapentaenoic acid: A potential protein-based platform for affinity purification of ω-3 lipids - Yuling Tang; Xunjiao Wei; Yonghua Wang; Wen Chen (Food Bioscience, 2025)

Target-activated DNAzyme and ion-functionalized DNA nanospheres enable dual cfDNA homogeneous electrochemical analysis for tuberculosis diagnosis - Yanming Meng; Runlian Qu; Yue Wang; Chunying Zhang; Wu Peng; Yuling Xiao; Hongxia Ruan; Hao Chen; Binwu Ying; Piaopiao Chen (Chemical Engineering Journal, 2025)

Momordica Charantia L.-derived extracellular vesicles achieve pancreatic-targeted delivery and repair insulin-secretory function through dual mechanisms via lymphatic transport - Meiqi Han; Jiahong Wang; Zihan Zhang; Ziwei Yan; Zhiqi Wang; Xinyao Guan; Siling Wang; Yuling Mao; Jinghai Zhang (Chemical Engineering Journal, 2025)

Portable aptasensor for smartphones using trimetallic PtPdAuNFs and triplex molecular switch for rapid detection of procymidone - Ruonan Wang; Baoshan He; Zhengyong Liang; Yuling Wang; Huali Jin; Min Wei; Wenjie Ren; Zhiguang Suo; Yiwei Xu (Chemical Engineering Journal, 2025)

A copper-doped mesoporous nanoplatform with dual enzyme-mimic activities for amplified cuproptosis and immune response - Qingqing Xu; Shuaipeng Feng; Yue Cao; Yang Li; Zhu Liu; Qiuling Deng; Jiaru Lan; Donghua Di; Yuling Mao; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Seasonal freeze-thaw significantly alters the distinct aquifers solute transport, microbial community assembly patterns, and molecular ecological networks in the hyporheic zone - Dong Li; Yuling Zhang; Xiaosi Su; Jili Wang; Ningfei Li (Water Research, 2025)

Ginger exosome-covered mesoporous polydopamine nanoplatform ameliorates liver fibrosis via antioxidation and macrophage phenotypic transformation - Junhong Zhou; Hongwei Xu; Zhu Liu; Yuling Mao; Yian Li; Liwan He; Shuaipeng Feng; Donghua Di; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Construction of yeast two-hybrid cDNA library and identification of interacting protein with McHDRa/b in Matricaria chamomilla L. - Honggang Wang; Luyao Yu; Shuangshuang Li; Jin Wang; Wenjing Cheng; Siqing Zhu; Feng Shi; Yuling Tai; Yi Yuan (Plant Molecular Biology, 2025)

Characteristic analysis of floc size distribution and image texture evolution in chemical coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Process Safety and Environmental Protection, 2025)

Efficient large-scale vegetation mapping at the formation level using multi-source data: A case study in Beijing, China - Jiachen Xu; Yongmei Huang; Kai Cheng; Yi Wang; Tianyu Hu; Hongcan Guan; Yuling Chen; Yu Ren; Mengxi Chen; Zekun Yang; Jiarui Wang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Characteristics of lipid accumulation induced by high-altitude environment improve the total antioxidant capacity of Ophiocordyceps sinensis - Tao Wang; Chuyu Tang; Mengjun Xiao; Min He; Yuling Li; Xiuzhang Li (Food Chemistry, 2025)

Encapsulation of cinnamaldehyde with protein-based nanoemulsions for strawberry preservation: Influence of protein types - Jiayan Lu; Yunyan Hua; Mengjia Guo; Laixue Ni; Yuling Cai; Yungang Cao; Longfeng Wang; Weiwei Li (Food Packaging and Shelf Life, 2025)

Water stress exacerbated by altered flow pathways in the Tibetan plateau: A critical analysis - Yuling Ren; Saurabh Mishra; Yanqing Lian; Jianyun Zhang; Junliang Jin; Ke Zhang; Weiguang Wang; Yongliang Gao; Yashuo Guan; Muwu Ling; Xiaonan Sun (Environmental Impact Assessment Review, 2025)

Mineral-element-chelating activity of food-derived peptides: influencing factors and enhancement strategies - Chaonan Cai; Yuting Liu; Yuling Xu; Juntao Zhang; Benmei Wei; Chengzhi Xu; Haibo Wang (Critical Reviews in Food Science and Nutrition, 2025)

Environmental impacts and carbon reduction benefits of mining photovoltaic systems: A case study of Ningdong coal base - Yongliang Zhang; Peixian Li; Ximin Cui; Guorui Wang; Yuling Zhao; Guangyao Zhu (Journal of Cleaner Production, 2025)

Black soldier fly larvae (Diptera: Stratiomyidae) enhance stabilization and modulate substrate microbial communities during municipal sewage sludge biotransformation - Weiping Tian; Zhouqiang Wang; Yu Xing; Yandong Xie; Yuling Jian; Haizhao Sun (Journal of Environmental Chemical Engineering, 2025)

Afforestation increases glomalin-related soil protein content and enhances its association with stable soil carbon in karst regions - Lei Xie; Qiumei Ling; Peilei Hu; Yuling Zhang; Wei Zhang; Yuan Zhao; Kelin Wang (Forest Ecology and Management, 2025)

Autotrophic Uranium (VI) bioreduction in groundwater by siderite: Comparison with sulfur and zero-valent iron - Yidan Zhang; Meng Ren; Chuanjin Xia; Wenzhong Wang; Yuling Zhu (Environmental Research, 2025)

Impact of conversion of coastal wetlands into paddy fields on the process of nitrite-dependent anaerobic methane oxidation - Qinan Hu; Weiqi Wang; Wangting Yang; Yuling Yang; Yanan Bai; Yefan He; Bingjie Ren; Yanping Wang; Jinghao Jin; Lidong Shen (Soil Ecology Letters, 2025)

Exogenous melatonin enhancing the accumulation of flavonoids and carotenoids in wolfberry fruit at cold storage - Rong Jiang; Zhiqiang Wang; Yixin Jia; A. Biao; Yuan Zong; Chao Yang; Minglin Li; Hongjiao Wang; Yuling Zhao; Ying Wang; Shaohua Zeng (Food Research International, 2025)

Cellulosic aerogel-encapsulated carbon dots for enhanced mercury detection and adsorption in aqueous systems with subsequent upcycling for organic pollutant photocatalytic degradation - Ming Li; Panpan Zhang; Jianwei Mao; Jianfeng Li; Dongqing Wang; Bo Xu; Jin Zhou; Jinghong Zhang; Qianyong Cao; Yuling Zhang; Huining Xiao (Desalination, 2025)

Microbial Life History Mediates the Drought‐Induced Decrease in Wood Decomposition in Subtropical Forests - Shuxian Jia; Xuhui Zhou; Yuling Fu; Guiyao Zhou; Lingyan Zhou; Xinxin Wang; Zheng Jiang; Jordi Sardans; Josep Penuelas (Ecology Letters, 2025)
Progressive intensification of drought regimes worldwide threatens wood decomposition ‐ a critical biogeochemical process in forest carbon cycling. However, the interactions between microbial strategies, wood traits and microclimate in regulating wood decomposition remain poorly understood under drought conditions. In a throughfall exclusion experiment (control 35% and 70% rainfall reduction) across 12 tree species, we found that drought‐induced reductions in wood CO 2 efflux rates were primarily driven by wood traits (density and carbon reduction) and shifts in fungal K / r ‐strategies. Coarse wood debris with higher Basidiomycota and lower Ascomycota abundance decomposed faster. Significant positive correlations were observed between fungal K / r ‐strategies and wood CO 2 efflux under control, 35%, and 70% rainfall reduction, while bacterial strategies showed no correlation. Our findings highlight the greater drought sensitivity of fungi than bacteria, emphasising their critical role in forest carbon dynamics and informing carbon models to improve the prediction of climate‐biosphere feedback in the changing world.

Conjugated Iminodibenzyl Dyes Incorporating Phenolic Hydroxyl Group and Strong Electron Donating or Accepting Groups for Facilitating ESIPT and Proton Transfer in Six- or Seven-Membered Cycles - Xiaozhuan Qin; Hongru Li; Yufei Wang; Yuling Li; Xiaochuan Li (Journal of Fluorescence, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Transcriptomics and metabolomics provide the difference of unique odor between natural and cultivated Ophiocordyceps sinensis and the biosynthetic pathway of key volatile compounds - Tao Wang; Mengjun Xiao; Chuyu Tang; Jianzhao Qi; Yuling Li; Xiuzhang Li (Food Bioscience, 2025)

Hierarchical MXene@PBA@IL nanohybrids towards high-efficiently enhance fire safety of epoxy resin - Jirui Qu; Gaoyuan Li; Biyu Huang; Haopeng Zhang; Yuling Wang; Richeng Lian; Lei Liu; Lei Yang; Baojun Li; Xilei Chen; Chuanmei Jiao (Chemical Engineering Journal, 2025)

Comparative transcriptomic analysis of heterotic maize development during kernel filling - Wenyu Li; Xiangkun Guo; Wen Yao; Keke Li; Qi Zheng; Yongbiao Yu; Zhiwei Zhang; Yan Wang; Weigang Yao; Ju Wu; Huan Hu; Lingwei Hu; et al. (Plant Molecular Biology, 2025)

Peptides from Dalian Stichopus japonicus: Antioxidant Activity and Melanogenesis Inhibition In Vitro Cell Models and In Vivo Zebrafish Models Guided by Molecular Docking Screening - Xue Li; Fanying Meng; Tong Sun; Zezhuang Hao; Yihua Wang; Yunfei Jiang; Ye Wang; Yong Li; Yuling Ding (Marine Biotechnology, 2025)

Prebiotic Peptide Synthesis: How Did Longest Peptide Appear? - Yuling Yang; Zhibiao Wang; Jin Bai; Hai Qiao (Journal of Molecular Evolution, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Conversion of coastal wetlands to paddy fields substantially decreases methane oxidation potential and methanotrophic abundance on the eastern coast of China - Yuling Yang; Weiqi Wang; Qinan Hu; Xiaochen Yao; Wangting Yang; Sile Wen; Haikun Wu; Jinghao Jin; Lidong Shen (Water Research, 2025)

Coniferous wood fossils as records of paleoecology, paleoclimatology, and paleoenvironment: A review - Leon Nahuel Torres; Xiao Shi; Yuling Na; Bing Wang; Chi Tian; Wenpei Pei; Yan Liu; Jianxin Yu (Review of Palaeobotany and Palynology, 2025)

Enhanced modeling of deep-water condensate transport and dispersion in the South China Sea - Qiuyan Wang; Yuling Lü; Xiaoming Luo; Xuerui Zang; Binxi Yue (Process Safety and Environmental Protection, 2025)

Evaluation of water vapor from CARRA reanalysis based on GNSS and radiosonde observation in the Arctic - Ce Zhang; Shuaimin Wang; Yuling Zhao; Yujing Xu; Jiajia Zhang; Yanhan Mo; Hong Yu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Encapsulation of oleanolic acid into cyclodextrin metal-organic frameworks by co-crystallization: Preparation, structure characterization and its effect on a zebrafish larva NAFLD model - Meng Li; Dongxia Hu; Dian Zhang; Guangya Xu; Di Wu; Chengcheng Gao; Linghan Meng; Xiao Feng; Weiwei Cheng; Zhenjiong Wang; Yuling Yang; Xiaozhi Tang (Food Research International, 2025)

Exploration on antifreeze potential of thawed drip enzymatic hydrolysates on myofibrillar proteins in pork patties during freeze-thaw cycles - Xiaoyu Han; Yang Li; Ying Wang; Jinpeng Wang; Wendi Teng; Longlong Dong; Yuling Cai; Jinxuan Cao; Yuemei Zhang (Food Chemistry, 2025)

Endogenous stem cell repair strategy via electromechanical interaction for stress injury - Honglin Xiang; Fan Wang; Qing Zhang; Zeyu Han; Yefei Lei; Neng Lai; Ke Jiang; Hanfeng Yang; Wenguo Cui; Yuling Li (Chemical Engineering Journal, 2025)

Improvement of plan quality in whole-breast radiation following BCS using feasibility DVH by less-experienced planners - Yun Zhang; Yuling Huang; Mingming Luo; Xingxing Yuan; Xiaoping Wang; Changfei Gong (Physical and Engineering Sciences in Medicine, 2025)
Variability in plan quality of radiotherapy is commonly attributed to the planner’s skill rather than technological parameters. While experienced planners can set reasonable parameters before optimization, less experienced planners face challenges. This study aimed to assess the quality of volumetric-modulated arc therapy (VMAT) in patients with left-sided breast cancer following breast-conserving surgery. Twenty-eight patients requiring whole-breast irradiation were randomly selected for inclusion. Each patient underwent two VMAT treatment plans: one optimized by an experienced planner (VMAT-EXP group) and the other designed by a less experienced planner using feasibility dose-volume histogram (FDVH) parameters from PlanIQ (VMAT-FDVH group). Both plans aimed to deliver a prescription dose of 50 Gy in 25 fractions to the planning target volume (PTV). Dosimetry parameters for the PTV and organs at risk (OARs) were compared between the two groups. Both the VMAT-EXP and VMAT-FDVH groups met the clinical plan goals for PTV and OARs. VMAT-FDVH demonstrated a PTV coverage and homogeneity comparable to those of VMAT-EXP. Compared to VMAT-EXP plans, VMAT-FDVH plans resulted in a significant reduction in the mean ipsilateral lung dose, with an average decrease of 0.9 Gy (8.5 Gy vs. 7.6 Gy, P < 0.001). The V5Gy and V20Gy of the ipsilateral lung were also reduced by 3.2% and 1.8%, respectively. Minor differences were observed in the heart, contralateral lung, breast, and liver. Personalized objectives derived from the feasibility DVH tool facilitated the generation of acceptable VMAT plans. Less experienced planners achieved lower doses to the ipsilateral lung while maintaining adequate target coverage and homogeneity. These findings suggest the potential for the effective use of VMAT in in patients with left-sided breast cancer following breast-conserving surgery, especially when guided by feasibility DVH parameters.

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Natural selection of Lacticaseibacillus paracasei mutant: Weaken the post-acidification of fermented milk - Lei Li; Han Lu; Yuling Xue; Yannan He; Baohua Zhao; Lianzhong Ai; Shijie Wang (Food Bioscience, 2025)

Constructing a low-cost total Ce(III)-based adsorbent for efficient removal and recovery of phosphate - Tao Zhang; Junle Li; Dongqing Liu; Yuling Ma; Yu Han; Sujie Shan; Kai Sun; Elena V. Zelinskaya; Aijie Wang; Hongliang Sun; Wei Wang (Chemical Engineering Journal, 2025)

Biochar supporting and sulfidation synergistically affect reactivity of nanoscale zerovalent iron towards sulfamethoxazole - Mi Li; Tiao Zhang; Jing Wang; Xiaoyu Xiao; Xinyi Zeng; Cui Hu; Xiaoming Zou; Wei Hui; Yuling Zheng (Chemical Engineering Journal, 2025)

The genus Quercus: metabolites, biological activity and mechanisms of action - Lulu Jiang; Shuanghui Yin; Guangyue Wang; Xinting Shao; Ye Wang; Yong Li; Yuling Ding (Phytochemistry Reviews, 2025)

Fabrication and characterizations of biodegradable films based on polysaccharide from Pyropia yezoensis waste with antioxidant and antibacterial activities - Xi Qiang; Yuling Song; Jianfeng Niu; Wenhui Gu; Xulei Wang; Songcui Wu; Yuhong Zhang; Lijun Wang; Guangce Wang (Journal of Applied Phycology, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Nuclear factor NF-YA4a regulates salt stress tolerance and juvenile-adult phase transition in Pyrus - Yingjie Yang; Yuling Mei; Xueping Li; Ran Wang; Chunhui Ma; Jiankun Song; Zhenhua Cui; Jianlong Liu; Xiaozhi Zhou; Dingli Li (Horticulture, Environment, and Biotechnology, 2025)

Trends in precipitable water vapor in North America based on GNSS observation and ERA5 reanalysis - Yuling Zhao; Ce Zhang; Shuaimin Wang; Yujing Xu; Hong Yu (Climate Dynamics, 2025)

Impact of white matter hyperintensity location on outcome in acute ischemic stroke patients: a lesion-symptom mapping study - Yuling Peng; Dan Luo; Peng Zeng; Bang Zeng; Yayun Xiang; Dan Wang; Ying Chai; Yongmei Li; Xiaoya Chen; Tianyou Luo (Brain Imaging and Behavior, 2025)

Eliminating the effect of pH: Dual-matrix modulation adsorbent enables efficient lithium extraction from concentrated seawater - Yu Han; Liuqian An; Yan Yang; Yuling Ma; Hongliang Sun; Jinxin Yao; Tao Zhang; Wei Wang (Water Research, 2025)

Transcriptomic analysis reveals the mechanism of ozone fumigation combined with polyethylene nanopackaging for delaying the browning and softening of mushrooms (Agaricus bisporus) - Biao Wang; Jianmin Yun; Weihong Guo; Jiawei Shen; Ting Wang; Fengyun Zhao; Yuling Qu; Liang Yao (Postharvest Biology and Technology, 2025)

Functional analysis of (E)-β-farnesene synthases involved in accumulation of (E)-β-farnesene in German chamomile (Matricaria chamomilla L.) - Yuling Tai; Haiyan Wu; Lu Yang; Yi Yuan; Youhui Chen; Honggang Wang; Yifan Jin; Luyao Yu; Shuangshuang Li; Feng Shi (Plant Science, 2025)

Oil/water interface behavior of hesperidin methylchalcone and its application in nano-emulsions - Yuxiang Wang; Benguo Liu; Yuling Ma; Chunyan Wang; Hanjun Ma; Sheng Geng (Food Chemistry, 2025)

Enzymatic browning of button mushrooms during postharvest cold chain circulation - Biao Wang; Ting Wang; Jianmin Yun; Yuling Qu; Xuerui Wang; Fengyun Zhao; Liang Yao (Food Bioscience, 2025)

Collagen IV/laminin-1 coated temozolomide-prodrug hydrogel for recruiting and eradicating residual glioma cells - Yufu Zhu; Jiaqi Jin; Yang Lu; Diancheng Hang; Xuefeng Zhang; Gang Zhao; Qing Wang; Yuling Li; Hongmei Liu (Chemical Engineering Journal, 2025)

A novel approach to estimate land surface temperature from landsat top-of-atmosphere reflective and emissive data using transfer-learning neural network - Shuo Xu; Dongdong Wang; Shunlin Liang; Aolin Jia; Ruohan Li; Zhihao Wang; Yuling Liu (Science of The Total Environment, 2024)

Responses of suspended sludge and biofilm in a SNAD system under C/N elevation: Microbial activity, nitrogen conversion flux and molecular ecological network - Junyu Liu; Meina Hu; Mei Hu; Jiaao Wang; Tingting Zhang; Yuling Wang; Xiaohui Wang (Science of The Total Environment, 2024)

Constructing a visual detection method for coagulation effect based on image feature machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Journal of Water Process Engineering, 2024)

Selective ion channel adsorbents facilitate efficient and low environmental impact extraction of liquid lithium resources - Yu Han; Yan Yang; Yuling Ma; Daxin Liang; Liping Wen; Jun Ma; Wei Wang (Journal of Hazardous Materials, 2024)

Lactobacillus plantarum LP104 improved intestinal and brain inflammation by modulating TLR4 pathway and gut flora in alcohol liver injury mice - Yue Zhang; Yuxuan Ma; Yuling Fan; Yuexin Gao; Yamei He; Yu Wang; Bo Nan; Jingsheng Liu; Xia Li; Yuhua Wang (Food Bioscience, 2024)

Potential adaptation of scleractinian coral Pocillopora damicornis during hypo-salinity stress caused by extreme pre-flood rainfall over south China - Junling Chen; Xiaopeng Yu; Kefu Yu; Biao Chen; Zhenjun Qin; Zhiheng Liao; Yuling Ma; Lijia Xu; Yongzhi Wang (Environmental Research, 2024)

Low-cost Ca/Mg co-modified biochar for effective phosphorus recovery: Adsorption mechanisms, resourceful utilization, and life cycle assessment - Ming Chen; Yifan Liu; Junchao Pan; Yuling Jiang; Xueyan Zou; Yangyang Wang (Chemical Engineering Journal, 2024)

NiCo layered double hydroxide anchored on MXene/tannin carbon cryogel composite with 3D hierarchical sea urchin-like structure for asymmetric supercapacitors - Yuling Lan; Shirui Wang; Zhanhui Yuan; Weigang Zhao (Chemical Engineering Journal, 2024)

Assessment of genetic diversity of Camellia yuhsienensis based on leaf structure and inter simple sequence repeat (ISSR) markers - Yuling Zou; Xiaoning Ge; Chao Yan; Qiuping Zhong; Danyang Chen; Zexin Chen; Yaqi Yuan; Hongyan Guo; Youcheng Zhou; Jinfeng Wang; Linqing Cao (Genetic Resources and Crop Evolution, 2024)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Highly efficient degradation of ethanol, acetaldehyde, and ethyl acetate removal by bio-trickling filter reactors with various fillers - Hairong Jiang; Yue Wang; Yuling Zhang; Yixuan Yang; Ruoqi Cui; Lianhai Ren; Minglu Zhang; Yongjing Wang (Process Safety and Environmental Protection, 2024)

Constructing a visual detection model for floc settling velocity using machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao (Journal of Environmental Management, 2024)

Design, construction and evaluation of collaborative bio-system of Vibrio fluvialis with Chlorella sorokiniana for treating actual printing and dyeing wastewater - Yuling Song; Lijun Wang; Xi Qiang; Menglin Guo; Wenhui Gu; Songcui Wu; Shan Gao; Xuehua Liu; Xiujun Xie; Quancheng Fan; Jing Zhang; Zengling Ma; et al. (Chemical Engineering Journal, 2024)

Stimulation of methane production potential and alteration in community composition of methanogens following conversion of China’s coastal marshes to paddy fields - Xiaochen Yao; Weiqi Wang; Yuling Yang; Wangting Yang; Qinan Hu; Jinghao Jin; Jiaqi Liu; Yuchao Wang; Lidong Shen (CATENA, 2024)

Population pharmacokinetics of fluconazole for prevention or treatment of invasive candidiasis in Chinese young infants - Honghong Wang; Dandan Li; Yongjiang Jiang; Jing Liang; Qiaoai Yu; Linghong Kuang; Yuling Huang; Dongjie Qin; Ping Li; Jing He; Feng Xu; Xueli Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Predicting the potential distribution of Arisaema heterophyllum in China under current and future climate change based on ArcGIS and MaxEnt model - Jing Xu; Yanan Wu; Shu Wang; Yuling Xu; Chaoyue Du; Emelda Rosseleena Rohani; Xiaohui Tong; Tongsheng Wang; Rongchun Han (Plant Biosystems, 2024)

A novel approach for quantifying the influence intensity of urban water and greenery resources on microclimate for efficient utilization - Fan Fei; Yuling Xiao; Luyao Wang; Yan Wang; Hiroatsu Fukuda; Wanxiang Yao; Haiming Yu; Qiwei Dong (Sustainable Cities and Society, 2024)

Vadose-zone characteristic pollutants distribution, microbial community structure and functionality changes in response to long-term leachate pollution of an informal landfill site - Dong Li; Yuling Zhang; Furong Yu; Jili Wang; Xinying Zhang; Liuyuan Feng; Tao Lang; Fengtian Yang (Science of The Total Environment, 2024)

Active role of iron-dependent AOM in paddy fields under different long-term fertilizer management schemes - Yuling Yang; Lidong Shen; Yuhan Jin; Yanan Bai; Shuwei Wang; Xu Zhao (Science of The Total Environment, 2024)

Effects of OSA-starch-fatty acid interactions on the structural, digestibility and release characteristics of high amylose corn starch - Mingyue Liu; Xiaoyan Wang; Yihui Li; Danni Jin; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Chemistry, 2024)

A new intracellularly regulated release pattern controlled by coordinated carrier cracking and drug release - Xinyue Zhang; Ye He; Zhiqi Wang; Ying Zhang; Wen Guo; Shuai Li; Xinyu Wang; Yuling Mao; Siling Wang (Chemical Engineering Journal, 2024)

A review of the research progress on Artemisia argyi Folium: botany, phytochemistry, pharmacological activities, and clinical application - Hailong Wang; Yiwen Zhang; Denghui Yu; Yong Li; Yuling Ding; Yuan He; Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Aging properties of polyethylene and polylactic acid microplastics and their adsorption behavior of Cd(II) and Cr(VI) in aquatic environments - Xinying Zhang; Yuling Zhang; Dong Li; Jili Wang; Yang Ding; Yiliang Wang; Liuyuan Feng; Yuliang Hu (Chemosphere, 2024)

The interplay of soil physicochemical properties, methanogenic diversity, and abundance governs methane production potential in paddy soil subjected to multi-decadal straw incorporation - Yuling Yang; Lidong Shen; Evgenios Agathokleous; Shuwei Wang; Yuhan Jin; Yanan Bai; Wangting Yang; Bingjie Ren; Jinghao Jin; Xu Zhao (Environmental Research, 2024)

Protective effects of the secondary metabolites from Quercus salicina Blume against gentamicin-induced nephrotoxicity in zebrafish (Danio rerio) model - Shuang-Hui Yin; Wen-Jun Zhang; Lu-Lu Jiang; Guang-Yue Wang; You-Jin Jeon; Yuling Ding; Yong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A pH transformable nanocarrier for gradual and precise delivery of a natural immunomodulator and chemotherapy agent to trigger tumor apoptosis - Qianwen Sun; Wei Chen; Qi Zhang; Yanqi Han; Yue Gao; Jun Ye; Hongliang Wang; Yi Zhang; Lili Gao; Yuling Liu; Yanfang Yang (Chemical Engineering Journal, 2024)

Epidemiologic trends and changes in humoral immunity and lymphocyte subsets levels among hospitalized children with Mycoplasma pneumoniae infection during 2019–2023 - Linyan Tang; Kaiwen Zheng; Lanlan Ma; Ling Chen; Yuling Zhao; Li Li; Ke Wang; Jing Zhang; Xing Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

N6-methyladenosine (m6A) Writer WTAP Potentiates Hepatocellular Carcinoma Immune Evasion and Aerobic Glycolysis - Fatao Yu; Yuling Feng; Qing Wang; Jian Sun (Cell Biochemistry and Biophysics, 2024)

The Footprints of Mitochondrial Fission and Apoptosis in Fluoride-Induced Renal Dysfunction - Qiyong Zuo; Lin Lin; Yuling Zhang; Mohammad Mehdi Ommati; Hongwei Wang; Jing Zhao (Biological Trace Element Research, 2024)

Monitoring nonlinear large gradient subsidence in mining areas through SBAS-InSAR with PUNet and Weibull model fusion - Yuanjian Wang; Ximin Cui; Chunqing Ge; Yuhang Che; Yuling Zhao; Peixian Li; Yue Jiang; Xiaoqing Han (Environmental Science and Pollution Research, 2024)

Design, construction and application of algae-bacteria synergistic system for treating wastewater - Weihao Li; Lijun Wang; Xi Qiang; Yuling Song; Wenhui Gu; Zengling Ma; Guangce Wang (Journal of Environmental Management, 2024)

Fungi and bacteria trade-off mediates drought-induced reduction in wood decomposition - Shuxian Jia; Tengfeng Yuan; Yuling Fu; Josep Penuelas; Guiyao Zhou; Lingyan Zhou; Dingqin Liu; Yanghui He; Ruiqiang Liu; Xinxin Wang; Bingqian Song; Zheng Jiang; et al. (CATENA, 2024)

Effects of soil aggregates and minerals on microbial necromass carbon are regulated by parent materials - Lei Xie; Peilei Hu; Qiumei Ling; Wei Zhang; Pengpeng Duan; Yuling Zhang; Kelin Wang (Applied Soil Ecology, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

Distribution, mobilization, risk assessment and source identification of heavy metals and nutrients in surface sediments of three urban-rural rivers after long-term water pollution treatment - Xu Yao; Zheng Wang; Dandan Li; Hejia Sun; Chong Ren; Yilei Yu; Feifei Pei; Yuling Li (Science of The Total Environment, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

Eliminating adverse effects of fouling layer using composite membranes with dense surface layers for sustainable membrane distillation of high-strength wastewater - Peizhi Wang; Jiawei Cheng; Jinxin Yao; Yuling Ma; Chuandong Wu; Dan Song; Wei Cheng; Jun Ma; Wei Wang (Desalination, 2024)

Pre-introducing Li4NiWO6 defect phase by tungsten modification enables highly stabilized Ni-rich cathode - Fanghui Du; Hanyu Qu; Xiaoxuan Yu; Lei Ding; Pengfang Zhang; Yan Wang; Yuling Chen; Yingchao Wang; Xitong Zhang; Junwei Zheng (Chemical Engineering Journal, 2024)

Plant regeneration in the new era: from molecular mechanisms to biotechnology applications - Chunli Chen; Yuxin Hu; Momoko Ikeuchi; Yuling Jiao; Kalika Prasad; Ying Hua Su; Jun Xiao; Lin Xu; Weibing Yang; Zhong Zhao; Wenkun Zhou; Yun Zhou; et al. (Science China Life Sciences, 2024)

Photocatalytic removal of ammonia nitrogen from water: investigations and challenges for enhanced activity - Huining Zhang; Yang Cao; Shaofeng Wang; Yuling Tang; Lihong Tian; Wenrui Cai; Zhiqiang Wei; Zhiguo Wu; Ying Zhu; Qi Guo (Environmental Science and Pollution Research, 2024)

Flotation mechanism and performance of air/condensate bubbles for removing oil droplets in the presence of acetic acid - Ce Wang; Yuling Lü; Hongwei Qi; Xiaoming Luo; Limin He (Science of The Total Environment, 2024)

South and Southeast Asia controls black carbon characteristics of Meili Snow Mountains in southeast Tibetan Plateau - Pengfei Chen; Shichang Kang; Yuling Hu; Tao Pu; Yajun Liu; Shijin Wang; Mukesh Rai; Ke Wang; Lekhendra Tripathee; Chaoliu Li (Science of The Total Environment, 2024)

3D visualization of oil-abundant limon flavedo layer under drying - Sara Shamim; Zhenting Wu; Yuling Tang; Jingru Jia; Chunju Liu; Haiou Wang; Fangcheng Zheng; Long Ba (Journal of Food Engineering, 2024)

EPR evidence of carrier effect on unpaired-electron number of Mn in SCR: The good, the bad, the ugly - Yixin Wang; Yuling Wen; Yihuan Zhang; Meijia Jiang; Jia Zhang; Guangren Qian (Fuel, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Antibiotic resistance, biofilm formation, and molecular epidemiology of Staphylococcus aureus in a tertiary hospital in Xiangyang, China - Yitong Tang; Na Xiao; JiuMing Zou; Yuling Mei; Yue Yuan; Menghuan Wang; Zezhou Wang; Yunjuan Zhou; Yiyuan Chen; Shichao Li (Brazilian Journal of Microbiology, 2024)

The ameliorative effect of probiotics on diet-induced lipid metabolism disorders: A review - Yu Wang; Zhiyi Ai; Xinyue Xing; Yuling Fan; Yue Zhang; Bo Nan; Xia Li; Yuhua Wang; Jingsheng Liu (Critical Reviews in Food Science and Nutrition, 2024)

A novel polyethylene nanopackaging combined with ozone fumigation delayed the browning and softening of Agaricus bisporus during postharvest storage - Biao Wang; Jianmin Yun; Chenguang Ye; Siya Xu; Weihong Guo; Fengyun Zhao; Yuling Qu; Yang Bi (Postharvest Biology and Technology, 2024)

Plowing drag-adaptive operation control method based on motor temperature compensation for electric tractor - Qi Wang; Xudong Wang; Wei Wang; Yongjie Cui; Yuling Song (Journal of Terramechanics, 2024)

Lithologic control of priming effect in subtropical forest - Tiangang Tang; Qi Zhang; Ruitong Fu; Pengpeng Duan; Yuling Zhang; Xinyi Yang; Kelin Wang; Dejun Li (CATENA, 2024)

Experimental study of building natural ventilation with pendulum velocity anemometer - Yuling Lv; Min Wang; Wentao Wu; Wenzhe Shang; Huimin Yao; Jianwei Li; Gerald DS. Quoie Jr; Hong Zhang; Xiong Shen (Building and Environment, 2024)

Near-full-length genome analysis of two novel HIV second recombinant forms in Hebei, China - Yuxin Feng; Jianhua Lu; Lijing Wang; Yuling Wang; Jingyun Li; Hanping Li; Lin Li; Erhei Dai (Archives of Virology, 2024)

First study on fossil wood from the Middle Pleistocene of the Songliao Plain, Northeast China - Leon Nahuel Torres; Xiao Shi; Yuling Na; Bing Wang; Chi Tian; Jun Chen (Review of Palaeobotany and Palynology, 2024)

Persulfate oxidation of norfloxacin by cobalt doped water hyacinth biochar composite: The key role of cobalt and singlet oxygen - Yunqiang Yi; Yue Fu; Yu Wang; Yuling Cai; Yifeng Liu; Zhimin Xu; Zenghui Diao (Journal of Water Process Engineering, 2024)

"Needle" hidden in silk floss: Inactivation effect and mechanism of melamine sponge loaded bismuth oxide composite copper-metal organic framework (MS/Bi2O3@Cu-MOF) as floating photocatalyst on Microcystis aeruginosa - Mengjiao Wang; Junfeng Chen; Yushan Wei; Lijun Hu; Yuling Xu; Yanyan Liu; Renjun Wang (Journal of Hazardous Materials, 2024)

Influence of aggregate characteristics on the plant growing environment of the planting concrete with SAC - Shanshan Jin; Yang Zhang; Yuling Yan; Zengmiao Xu; Aodong Li; Juan Wang; Pengfei Liu; Liuhuan Li; Zhihua Wang (Journal of Cleaner Production, 2024)

A multi-layer nanocased model to explain the U-shaped evolution of shale gas permeability at constant confining pressure - Wangxing Cheng; Guanglei Cui; Yuling Tan; Derek Elsworth; Chunguang Wang; Chengxiang Yang; Tianyu Chen; Chuanzhong Jiang (Fuel, 2024)

Variations of activity and community structure of nitrite-driven anaerobic methanotrophs in soils between native and invasive species in China's coastal wetlands - Jiaqi Liu; Weiqi Wang; Lidong Shen; Yanan Bai; Wangting Yang; Yuling Yang; Jiangbing Xu; Maohui Tian; Xin Liu; Jinghao Jin; Yuzhi Song (European Journal of Soil Biology, 2024)

Adaptive characteristics of indigenous microflora in an organically contaminated high salinity groundwater - Jili Wang; Yuling Zhang; Yang Ding; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Chemosphere, 2024)

Drought-induced changes in rare microbial community promoted contribution of microbial necromass C to SOC in a subtropical forest - Xinxin Wang; Lingyan Zhou; Yuling Fu; Zheng Jiang; Shuxian Jia; Bingqian Song; Dingqin Liu; Xuhui Zhou (Soil Biology and Biochemistry, 2024)

Equal importance of humic acids and nitrate in driving anaerobic oxidation of methane in paddy soils - Yanan Bai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Bingjie Ren; Wangting Yang; Yuling Yang; Zhiguo Ma; Zhaozhong Feng (Science of The Total Environment, 2024)

Fossil charcoal from the Upper Triassic Karamay Formation in the Junggar Basin, NW China, and its geological implications - Yuling Na; Leon Nahuel Torres; Xiao Shi; Bing Wang; Chi Tian; Jianxin Yu (Review of Palaeobotany and Palynology, 2024)

Research progress and trend of antibiotics degradation by electroactive biofilm: A review - Xinyi Zhang; Yuling Xu; Yanyan Liu; Yushan Wei; Feng Lan; Renjun Wang; Yuewei Yang; Junfeng Chen (Journal of Water Process Engineering, 2024)

Enhanced micro-explosion to improve the yield of light oil in catalytic cracking of water-in-heavy oil emulsion prepared by continuous membrane emulsification - Can Yuan; Ke Zhou; Yaxin Wang; Yuling Xie; Wenheng Jing; Weihong Xing (Fuel, 2024)

Fabrication and characterization of polyvinyl alcohol/sodium alginate loaded carvacrol/silica hollow microspheres composite hydrogel as a colourimetric freshness indicator - Hongdan Hao; Bingchao Duan; Lidan Zhang; Lan Wang; Lingli Zhang; Yufei Wang; Yuanyuan Li; Chunmei Zhao; Guochao Jia; Yuling Li; Congjun Liu; Kui Lu (Food Bioscience, 2024)

Nanozyme-mediated biocatalysis as a mitochondrial oxidative stress amplifier for tumor nanocatalytic immunotherapy - Junya Lu; Luming Song; Shuaipeng Feng; Kaili Wang; Yuling Mao; Yikun Gao; Qinfu Zhao; Siling Wang (Chemical Engineering Journal, 2024)

Eocene lacustrine microbialites in the western Qaidam Basin, China: implication for the sedimentary record and hydrocarbon potential - Xiang Li; Jiangong Wang; Guohui Long; Li Xu; Jun Cui; Xiujian Sun; Yuling Wang (Carbonates and Evaporites, 2024)

Diverse and high pollution of microplastics in seasonal snow across Northeastern China - Hanxuan Wen; Han Xu; Yuling Ma; Chunyu Zhang; Daizhou Zhang; Xin Wang (Science of The Total Environment, 2024)

Exploring low-carbon mulching strategies for maize and wheat on-farm: Spatial responses, factors and mitigation potential - Huihui Wei; Kaiping Zhang; Ning Chai; Yue Wang; Yuling Li; Jianjun Yang; Matthew Tom Harrison; Ke Liu; Pingxing Wan; Wenjuan Zhang; Guojun Sun; Zhansheng Li; et al. (Science of The Total Environment, 2024)

Smartphone-based electrochemical sensor for cost-effective, rapid and on site detection of chlorogenic acid in herbs using biomass-derived hierarchically porous carbon synthesized by a soft-hard dual template method - Wanjun Jiang; Zhonghui Zhuo; Xiaohua Zhang; Hai Luo; Lu He; Yuling Yang; Yangping Wen; Zhong Huang; Peng Wang (Food Chemistry, 2024)

The double heterostructure photocatalyst MoS2@ZIF-67/TiO2: Triumphant modification of TiO2 and efficient removal of Karenia mikimotoi - Yushan Wei; Junfeng Chen; Mengjiao Wang; Xinyi Zhang; Yuling Xu; Qingying Wei; Feng Lan; Peike Gao; Yanyan Liu; Renjun Wang (Chemical Engineering Journal, 2024)

Improving oxygen reduction reaction by cobalt iron-layered double hydroxide layer on nickel-metal organic framework as cathode catalyst in microbial fuel cell - Xinyi Zhang; Yuling Xu; Yanyan Liu; Yushan Wei; Feng Lan; Jiayu Wang; Xuemeng Liu; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2024)

Investigating alcohol consumption in China via wastewater-based epidemiology - Yan Yao; Jingya Wang; Yuling Zhong; Wenyu Chen; Yulan Rao; Mengxiang Su (Environmental Geochemistry and Health, 2024)

Research status and prospects of organic photocatalysts in algal inhibition and sterilization: a review - Yushan Wei; Renjun Wang; Mengjiao Wang; Lijun Hu; Xinyi Zhang; Yuling Xu; Yanyan Liu; Feng Lan; Junfeng Chen (Environmental Science and Pollution Research, 2023)

A biodegradable chitosan-based polymer for sustained nutrient release to stimulate groundwater hydrocarbon-degrading microflora - Jili Wang; Yuling Zhang; Ting Liu; Yujia Shi; Yang Ding; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Chemosphere, 2023)

Hydrothermal carbonization of biogas slurry and cattle manure into soil conditioner mitigates ammonia volatilization from paddy soil - Huiting Li; Detian Li; Shuhan Xu; Zhenqi Wang; Xu Chen; Yuling Ding; Qingnan Chu; Zhimin Sha (Chemosphere, 2023)

The selection of floating photocatalyst carrier and algae inhibition effect of Karenia mikimotoi based on SNP-TiO2@Cu-MOF under visible light - Renjun Wang; Lijun Hu; Mengjiao Wang; Yushan Wei; Yuling Xu; Xinyi Zhang; Junfeng Chen (Chemosphere, 2023)

Joint control method based on speed and slip rate switching in plowing operation of wheeled electric tractor equipped with sliding battery pack - Qi Wang; Xudong Wang; Wei Wang; Yuling Song; Yongjie Cui (Computers and Electronics in Agriculture, 2023)

Nitrogen fertilization rate affects communities of ammonia-oxidizing archaea and bacteria in paddy soils across different climatic zones of China - Bingjie Ren; Weiqi Wang; Lidong Shen; Wangting Yang; Yuling Yang; Jinghao Jin; Caiyu Geng (Science of The Total Environment, 2023)

Investigation on the mechanism of air/condensate bubble flotation of emulsified oil droplet - Ce Wang; Yuling Lü; Tianxu Ye; Li Chen; Limin He (Process Safety and Environmental Protection, 2023)

Role of condensate bubbles in enhancing oil droplets and organic acid flotation - Ce Wang; Yuling Lü; Tianxu Ye; Limin He (Journal of Water Process Engineering, 2023)

Research progress and prospect of metal-organic framework and covalent-organic framework for photocatalytic treatment of harmful algal blooms - Mengjiao Wang; Junfeng Chen; Yushan Wei; Lijun Hu; Yuling Xu; Yanyan Liu; Renjun Wang (Journal of Water Process Engineering, 2023)

Characterization, in vitro digestibility and release properties of starch-linoleic acid-sodium alginate composite film - Huirong Chen; Xiaoyan Wang; Danni Jin; Mingyue Liu; Xiaonian Wu; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Research International, 2023)

Correction: The States of Different 5-HT Receptors Located in the Dorsal Raphe Nucleus Are Crucial for Regulating the Awakening During General Anesthesia - HaiXiang Ma; LeYuan Gu; YuLing Wang; Qing Xu; Yuanli Zhang; WeiHui Shao; Qian Yu; XiTing Lian; Lu Liu; JiaXuan Gu; Na Ji; XiaoLing Liu; et al. (Molecular Neurobiology, 2023)

The States of Different 5-HT Receptors Located in the Dorsal Raphe Nucleus Are Crucial for Regulating the Awakening During General Anesthesia - HaiXiang Ma; LeYuan Gu; YuLing Wang; Qing Xu; Yuanli Zhang; WeiHui Shao; Qian Yu; XiTing Lian; Lu Liu; JiaXuan Gu; Na Ji; XiaoLing Liu; et al. (Molecular Neurobiology, 2023)

The delaying effect of a novel polyethylene nanopackaging on postharvest stipe elongation of Flammulina velutipes and its mechanism analysis - Yuxuan Zhao; Jianmin Yun; Biao Wang; Yuling Qu; Fengyun Zhao; Yang Bi (Postharvest Biology and Technology, 2023)

A chronostratigraphic and biostratigraphic framework for the Yanliao Biota of northeastern China: Implications for Jurassic terrestrial ecosystems and evolution - Yuling Li; Su-Chin Chang; Haichun Zhang; Jun Wang; Rui Pei; Daran Zheng; Yan Fang; Sidney R. Hemming (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

New age constraints on the Lower Cretaceous Jiufengshan Formation of Inner Mongolia, China and their implications for the spatiotemporal development of the Jehol Biota - Yuling Li; Daran Zheng; Xiaobo Li; Xiao Teng; Qianqi Zhang; Han Wang; Hao-Yang Lee; Bo Wang; Su-Chin Chang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Horizontal and vertical distribution of nitrate-driven anaerobic methane oxidation process in coastal wetlands under different plant species cover across southeast China - Wangting Yang; Weiqi Wang; Lidong Shen; Yanan Bai; Jiaqi Liu; Yuling Yang; Hechen Huang; Bingjie Ren (CATENA, 2023)

Synthesis and Performance of Imide-Based Small Molecules Containing Carbazole Groups with AIE Properties - Haina Wang; Hui Zhang; Tianzhi Yu; Yuling Zhao (Journal of Fluorescence, 2023)

Two 3D Ln(III)-MOFs Based on Phosphineoxide Ligand: Synthesis, Structure Luminescent and Photocatalytic Properties - Yuling Li; Kecheng Liu; Wenmin Zhang; Yingxin Wang; Baoyu Wang; Yufei Wang; Xiaochuan Li (Journal of Fluorescence, 2023)

Corrigendum to ’Silicon carbide microfiltration membranes for oil-water separation: Pore structure-dependent wettability matters’ [Water Research 216 (2022) 118270] - Qian Jiang; Yaxin Wang; Yuling Xie; Ming Zhou; Qilin Gu; Zhaoxiang Zhong; Weihong Xing (Water Research, 2023)

Long-term fertilization enhances the activity of anaerobic oxidation of methane coupled to nitrate reduction and associated microbial abundance in paddy soils - Yuling Yang; Lidong Shen; Xu Zhao; Evgenios Agathokleous; Shuwei Wang; Bingjie Ren; Wangting Yang; Jiaqi Liu; Jinghao Jin; Hechen Huang; Hongsheng Wu (Soil Biology and Biochemistry, 2023)

Application of wastewater-based epidemiology to estimate the usage of beta-agonists in 31 cities in China - Yuling Zhong; Chenzhi Hou; Xinyi Gao; Mingyu Wang; Yan Yao; Mengyi Chen; Bin Di; Mengxiang Su (Science of The Total Environment, 2023)

Response characteristics of indigenous microbial community in polycyclic aromatic hydrocarbons (PAHs) contaminated aquifers under polyethylene microplastics stress: A microcosmic experimental study - Yang Ding; Jili Wang; Yuling Zhang; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Science of The Total Environment, 2023)

Relationship between carbon pool changes and environmental changes in arid and semi-arid steppe—A two decades study in Inner Mongolia, China - Hang Li; Banghui Yang; Yu Meng; Kai Liu; Shudong Wang; Dacheng Wang; Hongyan Zhang; Yuling Huang; Xingtao Liu; Dehui Li; Long Li; Xueke Li (Science of The Total Environment, 2023)

Wheat adaptation to environmental stresses under climate change: Molecular basis and genetic improvement - Hude Mao; Cong Jiang; Chunlei Tang; Xiaojun Nie; Linying Du; Yuling Liu; Peng Cheng; Yunfeng Wu; Huiquan Liu; Zhensheng Kang; Xiaojie Wang (Molecular Plant, 2023)

An overview of biological mechanisms and strategies for treating wastewater from printing and dyeing processes - Yuling Song; Lijun Wang; Xi Qiang; Wenhui Gu; Zengling Ma; Guangce Wang (Journal of Water Process Engineering, 2023)

Surface engineering based on element interdiffusion and interfacial reactions to boost the performance of LiCoO2 cathode material - Fanghui Du; Zhongxu Fan; Lei Ding; Yan Wang; Wenjing Shi; Jie Zhang; Hanyu Qu; Xiaoxuan Yu; Yuling Chen; Junwei Zheng (Chemical Engineering Journal, 2023)

Insights into electrogenerated intermediates and rapid screening of electrochemical reactions by surface-modified carbon fiber paper redox spray ionization mass spectrometry - Jiahui Bai; Mingmai Bao; Shanshan Wang; Tianlun Wen; Yuling Li; Jing Zhang; Tiansheng Mei; Yinlong Guo (Analytica Chimica Acta, 2023)

High-precision simultaneous measurement of 187Os, 186Os, and 184Os using 1013 Ω amplifiers and CDDs on NTIMS - Guiqin Wang; Yuling Zeng; Liang Qi; Wengui Liu; Jifeng Xu (Analytica Chimica Acta, 2023)

Signaling mechanisms underlying lymphatic vessel dysfunction in skin aging and possible anti-aging strategies - Yuling Yang; Xiuli Wang; Peiru Wang (Biogerontology, 2023)

Immunogenic response of recombinant pseudorabies virus carrying B646L and B602L genes of African swine fever virus in mice - Lishuang Deng; Sirui Gu; Yao Huang; Yuling Wang; Jun Zhao; Mincai Nie; Lei Xu; Siyuan Lai; Yanru Ai; Zhiwen Xu; Ling Zhu (Veterinary Microbiology, 2023)

Natural polysaccharide polymer network for sustained nutrient release to stimulate the activity of aromatic hydrocarbon-degrading indigenous microflora present in groundwater - Jili Wang; Yuling Zhang; Xi Wang; Siqi Yin; Ting Liu; Yujia Shi; Yang Ding; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Science of The Total Environment, 2023)

Intergenerational effects of parental [Cnmim]BF4 (n = 4, 6, 8) ionic liquids exposure on zebrafish development based on transcriptomic analysis - Yue Liu; Yanan Tian; Chenning Zhang; Xin Lu; Yuling Xue; Xinping Wang; Qiuyue Liao; Xin Li; Kai Lian; Jiaolong Huang; Jie Deng; Peng Duan (Science of The Total Environment, 2023)

Simulating oil droplet underwater dispersal from a condensate field spill in the South China Sea - Qiuyan Wang; Yuling Lü; Limin He; Xue Huang; Jiaxin Feng (Ocean Engineering, 2023)

Condensation of STM is critical for shoot meristem maintenance and salt tolerance in Arabidopsis - Xiuwei Cao; Qingwei Du; Yahe Guo; Ying Wang; Yuling Jiao (Molecular Plant, 2023)

Novel facile synthesis and room-temperature sintering of copper nanowires for solution-processed transparent conductive films - Qing Liu; Yibo Wu; Yong Li; Yuling Shi; Qianqian Pan; Danlong Yang; Tao Wang (Chemical Engineering Journal, 2023)

Manipulating polysulfide catalytic conversion through edge site construction, hybrid phase engineering, and Se anion substitution for kinetics-enhanced lithium-sulfur battery - Tong Li; Zhouhao Wang; Junping Hu; Haobin Song; Yuling Shi; Yu Jiang; Daohong Zhang; Shaozhuan Huang (Chemical Engineering Journal, 2023)

Unveiling the characteristics of popcorn by genome re-sequencing and integrating the ESTs and proteome data - Yongbin Dong; Fei Deng; Long Zhang; Xinyu Li; Qilei Wang; Yuling Li (Cereal Research Communications, 2023)

A new method for evaluating the synergistic effect of urban water body and vegetation in the summer outdoor thermal environment - Fan Fei; Luyao Wang; Yan Wang; Wanxiang Yao; Hiroatsu Fukuda; Yuling Xiao; Lei Tian; Tongtong Ji (Journal of Cleaner Production, 2023)

Relationship between antigenicity and allergenic epitopes of extensive hydrolyzed whey protein: LC-MS/MS-based analysis - Ying Wang; Feifei Yang; Yao Zheng; Yuling Xue; Zhiyuan Kang; Justyna Zulewska; Hongjuan Li; Hongbo Li; Jinghua Yu (Food Bioscience, 2023)

V-ATPase V0 subunit activation mediates maduramicin-induced methuosis through blocking endolysosomal trafficking in vitro and in vivo - Yuling Zheng; Jing Xiao; Junqi Wang; Bin Dong; Dawei Guo; Hui Ji; Haifeng Sun; Lin Peng; Shanxiang Jiang; Xiuge Gao (Food and Chemical Toxicology, 2023)

A novel oral biomimetic delivery system enhancing both the mucosal and systemic immunity of influenza virus vaccine - Hongyan Lu; Yikun Gao; Jianmin Chen; Jing Chai; Ansheng Li; Tongtong Sun; Yuling Mao; Ye He; Qinfu Zhao; Jinghai Zhang; Siling Wang (Chemical Engineering Journal, 2023)

Trace N-doped manganese dioxide cooperated with Ping-pong chrysanthemum-like NiAl-layered double hydroxide on cathode for improving bioelectrochemical performance of microbial fuel cell - Yuling Xu; Xinyi Zhang; Yanyan Liu; Yushan Wei; Feng Lan; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2023)

Comparative Analysis of the Therapeutic Effects of Fresh and Cryopreserved Human Umbilical Cord Derived Mesenchymal Stem Cells in the Treatment of Psoriasis - Zhifeng Wang; Yifan Hu; Xiaoyu Wang; Youdong Chen; Danfeng Wu; Houli Ji; Cuicui Yu; Jingmeng Fang; Chunrong Pan; Lianjian Wang; Shouxin Wang; Yinhong Guo; et al. (Stem Cell Reviews and Reports, 2023)

Microbubbles preparation by partial vaporization of low boiling condensate for crude oil/water separation - Ce Wang; Yuling Lü; Chao Song; Jiakai Shi; Peng Zhang; Limin He (Journal of Water Process Engineering, 2023)

Combustion and emission performance of a trapped-vortex gas turbine combustor fueled by RP-3 kerosene - Qian Wang; Mingyu Li; Yuling Zhao; Jiankun Xiao (Fuel, 2023)

Effect of amylose content and crystal type on the structure and digestibility of starch-fatty acid complex nanoparticle - Mingyue Liu; Xiaonian Wu; Xiaoyan Wang; Yuling Jiang; Zhengyu Huang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Structure, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

The effect of vacancy defective Mg (0001) surface on hydrogenation of Ni-Mg-CNTs: A mechanistic investigation - Congwen Duan; Mengmeng Wu; Xinya Wang; Dong Fu; Yuling Zhang; Wei Lv; Lianxi Hu; Ming Li; Fei Wang; Ying Wu (Fuel, 2023)

The miR156x + p/SPL13-6 module responds to ABA, IAA, and ethylene, and SPL13-6 participates in the juvenile–adult phase transition in Pyrus - Minyan Song; Anqi Li; Lei Sun; Yuling Mei; Zhiyan Wang; Rihong Wang; Ran Wang; Dingli Li; Jiankun Song; Chunxiang Zhang; Yingjie Yang (Horticulture, Environment, and Biotechnology, 2023)

Plant growth strategy determines the magnitude and direction of drought‐induced changes in root exudates in subtropical forests - Zheng Jiang; Yuling Fu; Lingyan Zhou; Yanghui He; Guiyao Zhou; Peter Dietrich; Jilan Long; Xinxin Wang; Shuxian Jia; Yuhuang Ji; Zhen Jia; Bingqian Song; et al. (Global Change Biology, 2023)
Root exudates are an important pathway for plant–microbial interactions and are highly sensitive to climate change. However, how extreme drought affects root exudates and the main components, as well as species‐specific differences in response magnitude and direction, are poorly understood. In this study, root exudation rates of total carbon (C) and its components (e.g., sugar, organic acid, and amino acid) were measured under the control and extreme drought treatments (i.e., 70% throughfall reduction) by in situ collection of four tree species with different growth rates in a subtropical forest. We also quantified soil properties, root morphological traits, and mycorrhizal infection rates to examine the driving factors underlying variations in root exudation. Our results showed that extreme drought significantly decreased root exudation rates of total C, sugar, and amino acid by 17.8%, 30.8%, and 35.0%, respectively, but increased root exudation rate of organic acid by 38.6%, which were largely associated with drought‐induced changes in tree growth rates, root morphological traits, and mycorrhizal infection rates. Specifically, trees with relatively high growth rates were more responsive to drought for root exudation rates compared with those with relatively low growth rates, which were closely related to root morphological traits and mycorrhizal infection rates. These findings highlight the importance of plant growth strategy in mediating drought‐induced changes in root exudation rates. The coordinations among root exudation rates, root morphological traits, and mycorrhizal symbioses in response to drought could be incorporated into land surface models to improve the prediction of climate change impacts on rhizosphere C dynamics in forest ecosystems.

Remediation of atrazine-contaminated soil in a fluidized-bed DBD plasma reactor - Nan Jiang; Ying Qu; Jinwei Zhu; Hongchang Wang; Ju Li; Yun Shu; Yutao Cui; Yuling Tan; Bangfa Peng; Jie Li (Chemical Engineering Journal, 2023)

Generation of condensate bubble aphrons (CBA) by partially vaporized condensate to enhance oil removal from produced water - Ce Wang; Yuling Lü; Tianxu Ye; Feng Rong; Limin He (Process Safety and Environmental Protection, 2023)

An integrated approach for quantifying source apportionment and source-oriented health risk of heavy metals in soils near an old industrial area - Chang Tan; Hao Wang; Qingchun Yang; Liyuan Yuan; Yuling Zhang; Jordi Delgado Martín (Environmental Pollution, 2023)

Premature mortality attributable to NO2 exposure in cities and the role of built environment: A global analysis - Jian Song; Yuling Wang; Qin Zhang; Wei Qin; Rubing Pan; Weizhuo Yi; Zhiwei Xu; Jian Cheng; Hong Su (Science of The Total Environment, 2023)

The effect of economic growth pressure on green technology innovation: Do environmental regulation, government support, and financial development matter? - Hongyang Yu; Jinchao Wang; Jian Hou; Bolin Yu; Yuling Pan (Journal of Environmental Management, 2023)

Large-scale metabolome analysis reveals dynamic changes of metabolites during foxtail millet grain filling - Tao Wang; Lu Xing; Hui Song; Yangyang Wei; Pengtao Li; Quanwei Lu; Nan Hu; Yuling Liu; Yongqing Zhao; Jinrong Liu; Baohong Zhang; Renhai Peng (Food Research International, 2023)

A negative-response strain sensor towards wearable microclimate changes for body area sensing networks - Jing Liu; Junze Zhang; Zeyu Zhao; Yanping Liu; Wai Cheong Tam; Zhaozhu Zheng; Xiaoqin Wang; Yuling Li; Zekun Liu; Yi Li; Gang Li (Chemical Engineering Journal, 2023)

GRK5 Deficiency in the Hippocampus Leads to Cognitive Impairment via Abnormal Microglial Alterations - Hongtao Shen; Tianzhen Zhang; Yao Ji; Yu Zhang; Yongxiang Wang; Yuling Jiang; Xiongjin Chen; Qiuhao Liang; Kefeng Wu; Yunfeng Li; Xingyu Lu; Lili Cui; et al. (Molecular Neurobiology, 2023)

Immobilizing arsenic in soil via amine metal complex: a case study using iron-ethylenediamine - Qilin Lv; Tairan Zhou; Tianhao Wang; Shuhan Wang; Yanning Ge; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

Pollution in river tributaries restricts the water quality of ecological water replenishment in the Baiyangdian watershed, China - Xu Yao; Zheng Wang; Wei Liu; Yao Zhang; Tianhe Wang; Yuling Li (Environmental Science and Pollution Research, 2023)

The increased medical burden associated with frailty is partly attributable to household solid fuel: A nationwide prospective study of middle-aged and older people in China - Xiaoyu Jin; Yuling Wang; Yudong Wu; Yunfeng Liang; Yuxuan Li; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Junwen Tao; Jian Song; Rubing Pan; Weizhuo Yi; et al. (Science of The Total Environment, 2023)

Water deficit aggravated the inhibition of photosynthetic performance of maize under mercury stress but is alleviated by brassinosteroids - Yulou Tang; Junjie Zhang; Lijuan Wang; Hao Wang; Haochi Long; Liuyang Yang; Gengwei Li; Jiameng Guo; Yongchao Wang; Yuling Li; Qinghua Yang; Weiyu Shi; et al. (Journal of Hazardous Materials, 2023)

Estimating the prevalence of hypertension in 164 cities in China by wastewater-based epidemiology - Chenzhi Hou; Yuling Zhong; Lan Zhang; Muyuan Liu; Fang Yan; Mengyi Chen; Youmei Wang; Peng Xu; Mengxiang Su; Chi Hu; Bin Di (Journal of Hazardous Materials, 2023)

Interaction mechanism between zein and β-lactoglobulin: Insights from multi-spectroscopy and molecular dynamics simulation methods - Chengzhi Liu; Nan Lv; Yuling Song; Lijuan Dong; Min Huang; Qing Shen; Gerui Ren; Ruibo Wu; Binju Wang; Zexing Cao; Hujun Xie (Food Hydrocolloids, 2023)

Hyperspectral imaging combined with chemometrics for rapid detection of talcum powder adulterated in wheat flour - Hong-Ju He; Yan Chen; Guanglei Li; Yuling Wang; Xingqi Ou; Jingli Guo (Food Control, 2023)

A newly developed consortium with a highly efficient thiocyanate degradation capacity: A comprehensive investigation of the degradation and detoxification potential - Xiaoshuang Xiao; Xuejiao An; Yuling Jiang; Liuwei Wang; Zelin Li; Fenju Lai; Qinghua Zhang (Environmental Pollution, 2023)

Comparing the indigenous microorganism system in typical petroleum-contaminated groundwater - Jili Wang; Yuling Zhang; Yang Ding; Hewei Song; Ting Liu; Yi Zhang; Weiqing Xu; Yujia Shi (Chemosphere, 2023)

Atmospheric particulate matter impairs cognition by modulating synaptic function via the nose-to-brain route - Chunmei Liang; Yuling Jiang; Tianzhen Zhang; Yao Ji; Yu Zhang; Yuanhong Sun; Shengnan Li; Yi Qi; Yan Wang; Yujie Cai; Tianwen Lai; Lili Cui (Science of The Total Environment, 2023)

Four decades of hydrological response to vegetation dynamics and anthropogenic factors in the Three-North Region of China and Mongolia - Dehui Li; Kai Liu; Shudong Wang; Taixia Wu; Hang Li; Yong Bo; Hongyan Zhang; Yuling Huang; Xueke Li (Science of The Total Environment, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Photocatalytic degradation effect and mechanism of Karenia mikimotoi by non-noble metal modified TiO2 loading onto copper metal organic framework (SNP-TiO2@Cu-MOF) under visible light - Lijun Hu; Junfeng Chen; Yushan Wei; Mengjiao Wang; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Journal of Hazardous Materials, 2023)

Heterogeneous interfacial photocatalysis for the inactivation of Karenia mikimotoi by Bi2O3 loaded onto a copper metal organic framework (Bi2O3@Cu-MOF) under visible light - Mengjiao Wang; Junfeng Chen; Lijun Hu; Yushan Wei; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Chemical Engineering Journal, 2023)

Experimental study on adsorption removal of SO2 in flue gas by defective UiO-66 - Yuling Ma; Airong Li; Cheng Wang (Chemical Engineering Journal, 2023)

Synergistic effect of CoOx and Ni-Co alloy in Ni-Co/SAPO-11 catalysts for the deoxygenation of stearic acids - Dejiang Zheng; Delin Guo; Zhongxu Wang; Xiaosheng Wang; Yuling Shan; Xinmei Liu; Zifeng Yan; Shitao Yu; Yuxiang Liu (Chemical Engineering Journal, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

Spatial scale transformation–based estimation model for fresh grass yield: a case study of the Xilingol Grassland, Inner Mongolia, China - Haixin Liu; Anbing Zhang; Yuling Zhao; Anzhou Zhao; Dongli Wang (Environmental Science and Pollution Research, 2023)

A critical review of research progress for metal alloy materials in hydrogen evolution and oxygen evolution reaction - Yuling Xu; Xinyi Zhang; Yanyan Liu; Renjun Wang; Yuewei Yang; Junfeng Chen (Environmental Science and Pollution Research, 2022)

A method for evaluating drug penetration and absorption through isolated buccal mucosa with highly accuracy and reproducibility - Shuangqing Wang; Lei Liu; Saige Meng; Yuling Wang; Daofeng Liu; Zhonggao Gao; Along Zuo; Jianpeng Guo (Drug Delivery and Translational Research, 2022)

Response of potential activity, abundance and community composition of nitrite‐dependent anaerobic methanotrophs to long‐term fertilization in paddy soils - Yuling Yang; Lidong Shen; Yanan Bai; Xu Zhao; Shuwei Wang; Jiaqi Liu; Xin Liu; Maohui Tian; Wangting Yang; Jinghao Jin; Hechen Huang; Hongsheng Wu (Environmental Microbiology, 2022)
The process of nitrite‐dependent anaerobic methane oxidation (n‐damo) catalysed by Candidatus Methylomirabilis oxyfera ( M . oxyfera )‐like bacteria is a novel pathway in regulating methane (CH 4 ) emissions from paddy fields. Nitrogen fertilization is essential to improve rice yields and soil fertility; however, its effect on the n‐damo process is largely unknown. Here, the potential n‐damo activity, abundance and community composition of M . oxyfera ‐like bacteria were investigated in paddy fields under three long‐term (32 years) fertilization treatments, i.e. unfertilized control (CK), chemical fertilization (NPK) and straw incorporation with chemical fertilization (SNPK). Relative to the CK, both NPK and SNPK treatments significantly ( p M . oxyfera ‐like bacteria. The variation of soil organic carbon (OrgC) content and inorganic nitrogen content caused by the input of chemical fertilizers and straw returning were identified as the key factors affecting the potential n‐damo activity and the abundance of M . oxyfera ‐like bacteria. However, the community composition and diversity of M . oxyfera ‐like bacteria did not change significantly by the input of fertilizers. Overall, our results provide the first evidence that long‐term fertilization greatly stimulates the n‐damo process, indicating its active role in controlling CH 4 emissions from paddy fields.

A new challenge in melon resistance breeding: the ToLCNDV case - Lampros Siskos; Lei Cui; Chen Wang; Richard G. F. Visser; Yuling Bai; Henk J. Schouten (Euphytica, 2022)
Tomato leaf curl New Dehli virus (ToLCNDV) is a whitefly transmitted plant virus that is affecting European melon cultivation for over a decade. Since its first introduction in the Mediterranean basin the virus has been associated with significant economic losses including lower yields and cracked non-marketable fruits in Spain and other key cucurbits production areas. Since there is no chemical application against viral pathogens the focus is geared towards resistance breeding. Various QTLs associated with ToLCNDV resistance have been reported over the recent years in melon and other cucurbits. In the current review we summarize the latest advances in melon breeding for ToLCNDV resistance and present all relevant loci known so far in cucurbits. As a way forward in the future we propose an alternative to traditional resistance gene introgression breeding by exploiting the knowledge on genes that confer susceptibility to the virus in melon and other cucurbits.

Research progress of photocatalysis for algae killing and inhibition: a review - Lijun Hu; Renjun Wang; Mengjiao Wang; Yuling Xu; Chao Wang; Yanyan Liu; Junfeng Chen (Environmental Science and Pollution Research, 2022)

Preparation of formate-free PMA@MOF-808 catalysts for deep oxidative desulfurization of model fuels - Cheng Wang; Airong Li; Yuling Ma; Shenglan Qing (Environmental Science and Pollution Research, 2022)

Human umbilical cord-derived mesenchymal stem cells ameliorate psoriasis-like dermatitis by suppressing IL-17-producing γδ T cells - Youdong Chen; Yifan Hu; Xue Zhou; Zihan Zhao; Qian Yu; Zeyu Chen; Yuanyuan Wang; Peng Xu; Zengyang Yu; Chunyuan Guo; Xilin Zhang; Yuling Shi (Cell and Tissue Research, 2022)

Research on Transfer Rate of Heavy Metals and Harmful Elements in Traditional Chinese Medicine Extraction and Refining Processes and Product Health Risk Assessment - Dujia Jin; Lin Li; Wujun Dong; Xiangyang Zhu; Xuejun Xia; Renyun Wang; Jun Ye; Ran Li; Zhihua Liu; Xueqing Xu; Lili Gao; Yuling Liu; et al. (Biological Trace Element Research, 2022)

The importance of compound-specific radiocarbon analysis in source identification of polycyclic aromatic hydrocarbons: A critical review - Miaolei Ya; Yuling Wu; Xinhong Wang; Yongyu Li; Guanyong Su (Critical Reviews in Environmental Science and Technology, 2022)

A review on submarine oil and gas leakage in near field: droplets and plume - Qiuyan Wang; Yuling Lü; Qigui Li (Environmental Science and Pollution Research, 2022)

PiRNA pathway in the cardiovascular system: a novel regulator of cardiac differentiation, repair and regeneration - Yuling Zhou; Ya Fang; Cuilian Dai; Yan Wang (Journal of Molecular Medicine, 2021)

The relative importance of soil moisture in predicting bacterial wilt disease occurrence - Gaofei Jiang; Ningqi Wang; Yaoyu Zhang; Zhen Wang; Yuling Zhang; Jiabao Yu; Yong Zhang; Zhong Wei; Yangchun Xu; Stefan Geisen; Ville-Petri Friman; Qirong Shen (Soil Ecology Letters, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

The comparative impact among different intensive statins and combination therapies with niacin/ezetimibe on carotid intima-media thickness: a systematic review, traditional meta-analysis, and network meta-analysis of randomized controlled trials - Hongwei Li; Xiaolin Xu; Liming Lu; Runlu Sun; Qi Guo; Qian Chen; Junjie Wang; Zhijian He; Yuling Zhang (European Journal of Clinical Pharmacology, 2021)

Protective effects of SP600125 on mice infected with H1N1 influenza A virus - Yuling Tang; Guanghui Yang; Yuxiang Li; Ming Wang; Gebin Li; Yanxin Hu (Archives of Virology, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Meta-analysis of the effect of the overexpression of aquaporin family genes on the drought stress response - Jianhong Ren; Xiaoxiao Yang; Chunying Ma; Yuling Wang; Juan Zhao; Le Kang (Plant Biotechnology Reports, 2021)

Correction to: The Preliminary Study on the Association Between PAHs and Air Pollutants and Microbiota Diversity - Jinye Hu; Yuling Bao; Yuqi Zhu; Ranagul Osman; Mengfan Shen; Zhan Zhang; Li Wang; Shuyuan Cao; Lei Li; Qian Wu (Archives of Environmental Contamination and Toxicology, 2021)

TMEM166 inhibits cell proliferation, migration and invasion in hepatocellular carcinoma via upregulating TP53 - Jiejie Yang; Bin Wang; Qian Xu; Yuling Yang; Lin Hou; Kan Yin; Qingming Guo; Yanan Hua; Li Zhang; Yixuan Li; Jinyu Zhang; Ning Li (Molecular and Cellular Biochemistry, 2021)

Analysis of microbial community structure and degradation of ammonia nitrogen in groundwater in cold regions - Shuo Li; Yuling Zhang; Siqi Yin; Xi Wang; Ting Liu; Zhiqun Deng (Environmental Science and Pollution Research, 2020)

MiR-221-3p regulates the microvascular dysfunction in diabetic retinopathy by targeting TIMP3 - Chongxian Wang; Yuling Lin; Yanqin Fu; Dongming Zhang; Yaping Xin (Pflügers Archiv - European Journal of Physiology, 2020)

The Preliminary Study on the Association Between PAHs and Air Pollutants and Microbiota Diversity - Jinye Hu; Yuling Bao; Yuqi Zhu; Ranagul Osman; Mengfan Shen; Zhan Zhang; Li Wang; Shuyuan Cao; Lei Li; Qian Wu (Archives of Environmental Contamination and Toxicology, 2020)

An interactive motion-tracking system for home-based assessing and training reach-to-target tasks in stroke survivors—a preliminary study - Wenke Fan; Yuling Zhang; Qing Mei Wang; Yulong Bai; Yi Wu (Medical & Biological Engineering & Computing, 2020)

Inhibitory effects of Dulcitol on rat C6 glioma by regulating autophagy pathway - Yuling Zhang; Hui Wang; Fangjuan Li; Xinxin Xu; Baogui Chen; Tao Zhang (Natural Product Research, 2020)

A Novel Self-Assembly Nanocrystal as Lymph Node-Targeting Delivery System: Higher Activity of Lymph Node Targeting and Longer Efficacy Against Lymphatic Metastasis - Yuling Mao; Jun Liu; Tianyu Shi; Ge Chen; Shujun Wang (AAPS PharmSciTech, 2019)

Osteogenic and angiogenic characterization of mandible and femur osteoblasts - Xue Yang; Jun Jiang; Ling Zhou; Song Wang; Mengjiao He; Kai Luo; Yuling Chen; Xiongcheng Xu (Journal of Molecular Histology, 2019)

Differential magnitude of rhizosphere effects on soil aggregation at three stages of subtropical secondary forest successions - Ruiqiang Liu; Xuhui Zhou; Jiawei Wang; Junjiong Shao; Yuling Fu; Chao Liang; Enrong Yan; Xiaoyong Chen; Xihua Wang; Shahla Hosseini Bai (Plant and Soil, 2019)

The contribution of oxygen-containing functional groups to the gas-phase adsorption of volatile organic compounds with different polarities onto lignin-derived activated carbon fibers - Fanyue Meng; Min Song; Yuexing Wei; Yuling Wang (Environmental Science and Pollution Research, 2019)

Alginate-based composites for environmental applications: a critical review - Bing Wang; Yongshan Wan; Yuling Zheng; Xinqing Lee; Taoze Liu; Zebin Yu; Jun Huang; Yong Sik Ok; Jianjun Chen; Bin Gao (Critical Reviews in Environmental Science and Technology, 2019)

A quantitative assessment of the air pollution purification effect of a super strong cold-air outbreak in January 2016 in China - Yuling Hu; Shigong Wang; Guicai Ning; Ying Zhang; Jiaxin Wang; Ziwei Shang (Air Quality, Atmosphere & Health, 2018)

Response of Vegetation Productivity to Climate Change and Human Activities in the Shaanxi–Gansu–Ningxia Region, China - Haixin Liu; Anbing Zhang; Tao Jiang; Anzhou Zhao; Yuling Zhao; Dongli Wang (Journal of the Indian Society of Remote Sensing, 2018)

Genetic dissection of wheat panicle traits using linkage analysis and a genome-wide association study - Kai Liu; Xiaoxiao Sun; Tangyuan Ning; Xixian Duan; Qiaoling Wang; Tongtong Liu; Yuling An; Xin Guan; Jichun Tian; Jiansheng Chen (Theoretical and Applied Genetics, 2018)

Uncovering tea-specific secondary metabolism using transcriptomic and metabolomic analyses in grafts of Camellia sinensis and C. oleifera - Wei-Wei Deng; Jieyun Han; Yanbing Fan; Yuling Tai; Biying Zhu; Mengqian Lu; Rangjian Wang; Xiaochun Wan; Zheng-Zhu Zhang (Tree Genetics & Genomes, 2018)

Genetic Dissection of Wheat Kernel Hardness Using Conditional QTL Mapping of Kernel Size and Protein-Related Traits - Xiaoxiao Sun; Tongtong Liu; Tangyuan Ning; Kai Liu; Xixian Duan; Xuerong Wang; Qiaoling Wang; Yuling An; Xin Guan; Ji-Chun Tian; Jian-Sheng Chen (Plant Molecular Biology Reporter, 2018)

Characteristics of petroleum-contaminated groundwater during natural attenuation: a case study in northeast China - Hong Qian; Yuling Zhang; Jiali Wang; Chaoqun Si; Zaixing Chen (Environmental Monitoring and Assessment, 2018)

Determination and optimization of a strong promoter element from Bacillus amyloliquefaciens by using a promoter probe vector - Yuling Liao; Bin Wang; Yanrui Ye; Li Pan (Biotechnology Letters, 2018)

Optimization of the purine operon and energy generation in Bacillus amyloliquefaciens for guanosine production - Yuling Liao; Yanrui Ye; Bin Wang; Li Pan (Biotechnology Letters, 2017)

Temperature drop and the risk of asthma: a systematic review and meta-analysis - Xiaowei Cong; Xijin Xu; Yuling Zhang; Qihua Wang; Long Xu; Xia Huo (Environmental Science and Pollution Research, 2017)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Electromyographic evaluation of high-intensity elastic resistance exercises for lower extremity muscles during bed rest - Jonas Vinstrup; Sebastian Skals; Joaquin Calatayud; Markus Due Jakobsen; Emil Sundstrup; Matheus Daros Pinto; Mikel Izquierdo; Yuling Wang; Mette K. Zebis; Lars Louis Andersen (European Journal of Applied Physiology, 2017)

Vitamin E-rich Nanoemulsion Enhances the Antitumor Efficacy of Low-Dose Paclitaxel by Driving Th1 Immune Response - Jun Ye; Wujun Dong; Yanfang Yang; Huazhen Hao; Hengfeng Liao; Bangyuan Wang; Xue Han; Yiqun Jin; Xuejun Xia; Yuling Liu (Pharmaceutical Research, 2017)

Polybrominated diphenyl ethers, organochlorine pesticides, and polycyclic aromatic hydrocarbons in water from the Jiulong River Estuary, China: levels, distributions, influencing factors, and risk assessment - Yuling Wu; Xinhong Wang; Yongyu Li; Miaolei Ya; Hui Luo; Huasheng Hong (Environmental Science and Pollution Research, 2017)

Therapeutic potential of pro-angiogenic BPC157 is associated with VEGFR2 activation and up-regulation - Ming-Jer Hsieh; Hsien-Ta Liu; Chao-Nin Wang; Hsiu-Yun Huang; Yuling Lin; Yu-Shien Ko; Jong-Shyan Wang; Vincent Hung-Shu Chang; Jong-Hwei S. Pang (Journal of Molecular Medicine, 2017)

A highly Selective Fluorescent Sensor for Monitoring Cu2+ Ion: Synthesis, Characterization and Photophysical Properties - Stephen Opeyemi Aderinto; Yuling Xu; Hongping Peng; Fei Wang; Huilu Wu; Xuyang Fan (Journal of Fluorescence, 2017)

Remediation of Cr(VI)-Contaminated Soil Using the Acidified Hydrazine Hydrate - Yameng Ma; Fangfang Li; Yuling Jiang; Weihua Yang; Lv Lv; Haotian Xue; Yangyang Wang (Bulletin of Environmental Contamination and Toxicology, 2016)

Detecting land uplift associated with enhanced oil recovery using InSAR in the Karamay oil field, Xinjiang, China - Lingyun Ji; Yong Zhang; Qingliang Wang; Yuling Xin; Jin Li (International Journal of Remote Sensing, 2016)

Nanoscale zerovalent iron-mediated degradation of DDT in soil - Yuling Han; Nan Shi; Huifang Wang; Xiong Pan; Hua Fang; Yunlong Yu (Environmental Science and Pollution Research, 2016)

Study on the velocity structure of the crust in Southwest Yunnan of the north-south seismic belt—Results from the Menghai-Gengma-Lushui deep seismic sounding profile - ShuaiJun Wang; BaoJin Liu; JianShi Zhang; BaoFeng Liu; YuLing Duan; XiangHui Song; XiaoGuo Deng; CeJun Ma; YiRan Zang (Science China Earth Sciences, 2015)

Effects of epigallocatechin gallate on the cell-wall structure of Mycobacterial smegmatis mc 2 155 - Tieying Sun; Biaojie Qin; Mingchuan Gao; Yuling Yin; Changyuan Wang; Shizhu Zang; Xinli Li; Cuili Zhang; Yi Xin; Tao Jiang (Natural Product Research, 2015)

Detection of an inversion in the Ty-2 region between S. lycopersicum and S. habrochaites by a combination of de novo genome assembly and BAC cloning - Anne-Marie A. Wolters; Myluska Caro; Shufang Dong; Richard Finkers; Jianchang Gao; Richard G. F. Visser; Xiaoxuan Wang; Yongchen Du; Yuling Bai (Theoretical and Applied Genetics, 2015)

QTL identification and meta-analysis for kernel composition traits across three generations in popcorn - Yongbin Dong; Zhongwei Zhang; Qingling Shi; Qilei Wang; Qiang Zhou; Yuling Li (Euphytica, 2015)

Isolation and characterization of ZmERF1 encoding ethylene responsive factor-like protein 1 in popcorn (Zea mays L.) - Qingling Shi; Yongbin Dong; Dahe Qiao; Qilei Wang; Zhiyan Ma; Feifei Zhang; Qiang Zhou; He Xu; Fei Deng; Yuling Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Disruption of Circulating CD4+ T-Lymphocyte Subpopulations in Psoriasis Patients is Ameliorated by Narrow-Band UVB Therapy - Xiuxiu Wang; Guanghua Wang; Yu Gong; Yeqiang Liu; Junying Gu; Wenjuan Chen; Yuling Shi (Cell Biochemistry and Biophysics, 2015)

Phylogeography and evolution of a fungal–insect association on the T ibetan P lateau - Yongjie Zhang; Shu Zhang; Yuling Li; Shaoli Ma; Chengshu Wang; Meichun Xiang; Xin Liu; Zhiqiang An; Jianping Xu; Xingzhong Liu (Molecular Ecology, 2014)
Parasitoidism refers to a major form of interspecies interactions where parasitoids sterilize and/or kill their hosts typically before hosts reach reproductive age. However, relatively little is known about the evolutionary dynamics of parasitoidism. Here, we investigate the spatial patterns of genetic variation of Chinese cordyceps, including both the parasitoidal fungus Ophiocordyceps sinensis and its host insects. We sampled broadly from alpine regions on the Tibetan Plateau and obtained sequences on seven fungal and three insect DNA fragments from each of the 125 samples. Seven and five divergent lineages/cryptic species were identified within the fungus and host insects, respectively. Our analyses suggested that O . sinensis and host insects originated at similar geographic regions in southern Tibet/Yunnan, followed by range expansion to their current distributions. Cophylogenetic analyses revealed a complex evolutionary relationship between O. sinensis and its host insects. Significant congruence was found between host and parasite phylogenies and the time estimates of divergence were similar, raising the possibility of the occurrence of cospeciation events, but the incongruences suggested that host shifts were also prevalent. Interestingly, one fungal genotype was broadly distributed, consistent with recent gene flow. In contrast, the high‐frequency insect genotypes showed limited geographic distributions. The dominant genotypes from both the fungus and the insect hosts may represent ideal materials from which to develop artificial cultivation of this important Chinese traditional medicine. Our results demonstrate that both historical and contemporary events have played important roles in the phylogeography and evolution of the O. sinensis –ghost moth parasitoidism on the Tibetan Plateau.

The Ph-3 gene from Solanum pimpinellifolium encodes CC-NBS-LRR protein conferring resistance to Phytophthora infestans - Chunzhi Zhang; Lei Liu; Xiaoxuan Wang; Jack Vossen; Guangcun Li; Tao Li; Zheng Zheng; Jianchang Gao; Yanmei Guo; Richard G. F. Visser; Junming Li; Yuling Bai; et al. (Theoretical and Applied Genetics, 2014)

Novel antimicrobial metabolites produced by Sika deer-associated Actinomyces sp. JN411010 - Yujiao Tang; Yanmei Wang; Zhaohui Wang; Jing Zhang; Jianchun Qin; Quankai Wang; Lihua Yang; Lingzhi Xu; Yuling Ding; Yang Guo; Hongliang Li; Jingsi Li; et al. (Natural Product Research, 2013)

Fine mapping of the Ph-3 gene conferring resistance to late blight (Phytophthora infestans) in tomato - Chunzhi Zhang; Lei Liu; Zheng Zheng; Yuyan Sun; Longxi Zhou; Yuhong Yang; Feng Cheng; Zhonghua Zhang; Xiaowu Wang; Sanwen Huang; Bingyan Xie; Yongchen Du; et al. (Theoretical and Applied Genetics, 2013)

Genetic mapping of gummy stem blight (Didymella bryoniae) resistance genes in Cucumis sativus-hystrix introgression lines - Lina Lou; Hongying Wang; Chuntao Qian; Jia Liu; Yuling Bai; Jinfeng Chen (Euphytica, 2013)

Health Risk Assessment of Nitrate Contamination in Groundwater: A Case Study of an Agricultural Area in Northeast China - Xiaosi Su; Huang Wang; Yuling Zhang (Water Resources Management, 2013)

Induction of apoptosis in HepG2 cells by polysaccharide MEP-II from the fermentation broth of Morchella esculenta - Meili Hu; Yan Chen; Cui Wang; Huali Cui; Peilu Duan; Tianlong Zhai; Yuling Yang; Shaofei Li (Biotechnology Letters, 2013)

Erratum to: Flavokawain B induces apotosis of non-small cell lung cancer H460 cells via Bax-initiated mitochondrial and JNK pathway - JunXia An; YaRong Gao; Jing Wang; QiYu Zhu; YuLing Ma; Jian Wu; Jian Sun; YaXiong Tang (Biotechnology Letters, 2012)

Flavokawain B induces apoptosis of non-small cell lung cancer H460 cells via Bax-initiated mitochondrial and JNK pathway - JunXia An; YaRong Gao; Jing Wang; QiYu Zhu; YuLing Ma; Jian Wu; Jian Sun; YaXiong Tang (Biotechnology Letters, 2012)

Effects of physical and mental task demands on cervical and upper limb muscle activity and physiological responses during computer tasks and recovery periods - Yuling Wang; Grace P. Y. Szeto; Chetwyn C. H. Chan (European Journal of Applied Physiology, 2011)

Expression profile of human immune-responsive gene 1 and generation and characterization of polyclonal antiserum - Wei Xiao; Lan Wang; Ruijing Xiao; Mengjun Wu; Jinquan Tan; Yuling He (Molecular and Cellular Biochemistry, 2011)

Identification and mapping of quantitative resistance to late blight (Phytophthora infestans) in Solanum habrochaites LA1777 - Junming Li; Lei Liu; Yuling Bai; Richard Finkers; Feng Wang; Yongchen Du; Yuhong Yang; Bingyan Xie; Richard G. F. Visser; Adriaan W. van Heusden (Euphytica, 2011)

Pharmacokinetics of Anti-hepcidin Monoclonal Antibody Ab 12B9m and Hepcidin in Cynomolgus Monkeys - Jim J. Xiao; Wojciech Krzyzanski; Yow-Ming Wang; Hongyan Li; Mark J. Rose; Mark Ma; Yuling Wu; Beth Hinkle; Juan Jose Perez-Ruixo (The AAPS Journal, 2010)

Molecular cloning, sequence and expression analysis of ZmArf2, a maize ADP-ribosylation factor - Yanyang Liu; Junzhou Li; Yuling Li; Mengguan Wei; Qingxin Cui; Qilei Wang (Molecular Biology Reports, 2010)

QTL identification of grain protein concentration and its genetic correlation with starch concentration and grain weight using two populations in maize (Zea mays L.) - Yuling Li; Yanzhao Wang; Mengguan Wei; Xuehui Li; Jiafeng Fu (Journal of Genetics, 2009)

Effects of vegetation control on ecosystem water use efficiency within and among four grassland ecosystems in China - ZHONGMIN HU; GUIRUI YU; YULING FU; XIAOMIN SUN; YINGNIAN LI; PEILI SHI; YANFEN WANG; ZEMEI ZHENG (Global Change Biology, 2008)
Through 2–3‐year (2003–2005) continuous eddy covariance measurements of carbon dioxide and water vapor fluxes, we examined the seasonal, inter‐annual, and inter‐ecosystem variations in the ecosystem‐level water use efficiency (WUE, defined as the ratio of gross primary production, GPP, to evapotranspiration, ET) at four Chinese grassland ecosystems in the Qinghai‐Tibet Plateau and North China. Representing the most prevalent grassland types in China, the four ecosystems are an alpine swamp meadow ecosystem, an alpine shrub‐meadow ecosystem, an alpine meadow‐steppe ecosystem, and a temperate steppe ecosystem, which illustrate a water availability gradient and thus provide us an opportunity to quantify environmental and biological controls on ecosystem WUE at different spatiotemporal scales. Seasonally, WUE tracked closely with GPP at the four ecosystems, being low at the beginning and the end of the growing seasons and high during the active periods of plant growth. Such consistent correspondence between WUE and GPP suggested that photosynthetic processes were the dominant regulator of the seasonal variations in WUE. Further investigation indicated that the regulations were mainly due to the effect of leaf area index (LAI) on carbon assimilation and on the ratio of transpiration to ET ( T /ET). Besides, except for the swamp meadow, LAI also controlled the year‐to‐year and site‐to‐site variations in WUE in the same way, resulting in the years or sites with high productivity being accompanied by high WUE. The general good correlation between LAI and ecosystem WUE indicates that it may be possible to predict grassland ecosystem WUE simply with LAI. Our results also imply that climate change‐induced shifts in vegetation structure, and consequently LAI may have a significant impact on the relationship between ecosystem carbon and water cycles in grasslands.

A mixture model approach to the mapping of QTL controlling endosperm traits with bulked samples - Xuefeng Wang; Zhiqiu Hu; Wei Wang; Yuling Li; Yuan-Ming Zhang; Chenwu Xu (Genetica, 2007)

Global genome expression analysis of rice in response to drought and high-salinity stresses in shoot, flag leaf, and panicle - Junli Zhou; Xiangfeng Wang; Yuling Jiao; Yonghua Qin; Xigang Liu; Kun He; Chen Chen; Ligeng Ma; Jian Wang; Lizhong Xiong; Qifa Zhang; Liumin Fan; et al. (Plant Molecular Biology, 2007)

Distinct reorganization of the genome transcription associates with organogenesis of somatic embryo, shoots, and roots in rice - Ning Su; Kun He; Yuling Jiao; Chen Chen; Junli Zhou; Lei Li; Sulan Bai; Xueyong Li; Xing Wang Deng (Plant Molecular Biology, 2007)

Mechanistic study of modulation of SR Ca2+-ATPase activity by gangliosides GM1 and GM3 through some biophysical measurements - Yuling Wang; Zhaochun Tsui; Fuyu Yang (Glycoconjugate Journal, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)